Chemical constituents from the aerial parts of Clematis terniflora DC - Meng-Ya Chen; Zi-Han Zhu; Xin-Yu Yu; Ya-Ru Wu; Shi-Hui Qian; Zhen-Lin Li (Biochemical Systematics and Ecology, 2027)

Effects of exogenous application of Ursolic acid on apple cuticular wax biosynthesis and postharvest quality preservation - Wei-Teng You; Zi-Heng Wang; Zhi-Chao Meng; Kui-Tao Zhang; Qi Zhang; Xu Han; Hang Zhang; Xiao-Min Xue; Shang Wu; Han Jiang; Ya-Li Zhang; Yuan-Yuan Li (Postharvest Biology and Technology, 2026)

Chemical constituents of Clerodendrum mandarinorum and their chemotaxonomic significance - Shi-Ya Tian; Feng Li; Huai-Qin Liu; Yu Qiu; Wu-Feng Li; Guang-Yan Liang; Chun-Chun Wang; Xue-Long Yan; Shang-Gao Liao; Qin-Feng Zhu (Biochemical Systematics and Ecology, 2026)

Multiple magma sources and incremental assembly of the late Mesozoic Yunmengshan batholith, North China Craton: Constraints from zircon Hf-O isotopes and apatite geochemistry - Zi-Mu Li; Miao-Miao Ling-Hu; Shi Chen; Jin-Feng Sun; Ji-Heng Zhang; Ya-Dong Wu; Bao-Quan Zhou; Quan-Lin Hou; Jin-Hui Yang (Lithos, 2026)

Association of structural characteristics with immunostimulatory activity of pectic polysaccharides prepared from Tartary buckwheat sprouts by enzymatic degradation and partial acid hydrolysis - Lin Zhang; Bo Li; Xuan Gao; Mao-Qing Wang; Ya-Nan Cao; Mao-Ling Tan; Yi-Chen Hu; Liang Zou; Dan Li; Yong Deng; Jing-Wei Huang; Ding-Tao Wu (Food Research International, 2026)

Microalgae-based bioremediation of reverse osmosis concentrate (ROC): Mechanisms, techno-economic bottlenecks, and circular bioeconomy perspectives - Na-Hui Hao; Jun Li; Ya-Rong Qi; Zhuo Chen; Yu-Ming Wang; Yu-Jia Gao; Xu-Cheng Cai; Yu Hong; Hong-Ying Hu; Yin-Hu Wu (Desalination, 2026)

Development of a NIR fluorescent probe HDI based on Zinc-mediated competitive coordination for multidimensional detection of glyphosate in complex systems - Ya-Tong Liu; Xi-Yue Luo; Bu-Xiao Wu; Yi-Wen Cui; Jun-Wen Wang; Ying-Kai Yuan; Yue-Li Zou; Li-Xia Zhao (Journal of Environmental Chemical Engineering, 2026)

Recoverable millimeter-sized poly(ether-ether-ketone)-based adsorbent beads with multisite complexation for Co2+/Ni2+ removal from radioactive wastewater - Peng-De Yu; Yan-Lin Ren; Wen-Juan Wang; Ya-Juan Cai; Ting Yue; Ke-Xiao Sang; Yi-Xing Sun; Dan Wu; Zi-Hao Yang; Chuan-Zhe Zhao; Ying-Kang Li; Ya-Ge Wu; et al. (Journal of Environmental Chemical Engineering, 2026)

Synthesis and valorization of corn silk-derived carbon dots for antimicrobial fruit preservation - Yong-Ping Wen; Meng-Ting Wu; Kwang-Pyo Kim; Meng-Yi Chen; Jia-Hui Liu; Ya-Ping Li; An-Guo Wu; Xiang Li; Song-Zhi Xie; Die Gao; Jian-Ming Wu; Xiao-Gang Zhou (International Journal of Food Microbiology, 2026)

Interannual variability of secondary organic carbon driven by seasonal shifts in formation regimes in southern Taiwan - Jun-Fa Ye; Chih-Yu Chan; Jian-Xian Wu; Shi-Ya Tang; Tse-Lun Chen; Li-Hao Young; Yu-Chieh Ting; Yen-Ping Peng; Wei-Hsiang Chen; Ming-Yeng Lin; Si-Chee Tsay; Neng-Huei Lin; et al. (Atmospheric Environment, 2026)

Antioxidant Activity of Bioactive Peptides Derived from Ulva prolifera in HaCaT Cells and Zebrafish - Li-Ru Hong; Shuo-Qi Wang; Ting-Ting Wu; Zhi-Ru Chen; Mo Chen; Chun-Er Cai; Pei-Min He; Ya Zhao; Rui Jia (Marine Biotechnology, 2026)

Development of an in situ binding (ISB) method to evaluate the binding of Cry1Ac toxin to the larval midgut epithelium of Helicoverpa armigera - Qiming Sun; Fang Guan; Huiwen Shen; Kaixia Li; Yihua Yang; Ya-Zhou He; Yidong Wu (Pesticide Biochemistry and Physiology, 2026)

Probiotic fermentation enhances the antihypertensive activity of Astragali radix via redox-inflammation-endothelial interaction axis - Yue-Yue Liu; Zhen-Hui Pan; Ya-Li Zhao; Teng-Gen Hu; Hong Wu (Food Bioscience, 2026)

Comparison of food allergic immune responses in sensitized female and male Balb/c mouse induced by Lateolabrax japonicus tropomyosin - Meng-Si Li; Qing-Mei Liu; Fei Xia; Li-Qiang Zhong; Zhi-Qiang Chen; Ya-Ping Wu; Yu-Ni Liao; Gui-Xia Chen; Yi-Xiang Liu; Guang-Ming Liu (Food and Chemical Toxicology, 2026)

Study on the mechanism of synergistic adsorption of CO2 and Hg0 by Mg-MOF-74-derived modified composites based on experiment and density functional theory - Peng Cheng; Li Jia; Jia-hao Zhao; Ya-wen Wu; Yue Yu; Xiao-fang Gao; Qing Meng; Yan Jin (Chemical Engineering Journal, 2026)

Modeling and analysis of structural effects and detection characteristics for a new toroidal coil–excited lateral resistivity logging-while-drilling (LWD) tool - Ya-Ping Zheng; Wei Xu; Hao Li; Yong-Song Zheng; Wei-Ping Wu; Ze-Hua Yan; Xin Li; Min Liu (Applied Geophysics, 2026)

Quantitative evaluation method of dual laterolog for fracture parameters in carbonate reservoirs in the Sichuan Basin - Qiang Lai; Ben-Jian Zhang; Hang Zhang; Yu-Yu Wu; Wei Xu; Jun Tang; Li Shen; Ya-Ping Zheng (Applied Geophysics, 2026)

Regulation mechanism of N2O and CH4 emissions during the pig manure composting amended with Polygonum Multiflorum Thunb - Ya-jun Duan; Hong-sheng Wu; Jiang-yu Yang; Zheng-tong Zhou; Tao-ran Shi; Cheng Cheng; Zhen-wei Li; Chun-fa Wu; Ming-chun Di; Yu-dong He; Feng-yi Hu (World Journal of Microbiology and Biotechnology, 2026)

The cytokinin oxidase/dehydrogenase MdCKX4 regulates drought tolerance in Malus domestica - Tong Li; Yu-Feng Zhang; Joy Xin-Yue Zhai; Zi-Quan Feng; Shuo Ma; Xin-Yi Li; Huai-Na Gao; Long-Xin Luo; Zhi Li; Qi Zhang; Min-Min Zhou; Ya-Li Zhang; et al. (Plant Science, 2026)

Identifying driving factors of lacustrine groundwater discharge in Lake Taihu with integrated surface-subsurface numerical modeling - Hao Zhou; Yadong Shi; Yue Zou; Ya Jiang; Na Zheng; Subin Cheng; Donghao Wu; Xin Luo; Chaomeng Dai; Juntao Zheng; Zhi Li (Journal of Hydrology, 2026)

Nano-assembly of dioscin via zein–Angelica sinensis polysaccharide composite nanocarriers: structure, stability, bioaccessibility and bioactivity - Tian-Le Mao; Yue Wu; Zhi-Xin Xu; Fan Yang; Jing Li; Xin Guo; Qian-Lan Wu; Ya-Fang Shang; Kiran Thakur; Yi-Long Ma; Zhao-Jun Wei (Food Chemistry, 2026)

Dopamine-coated LTO particles immobilized in PVA with directional dendritic channels for fast and selective lithium capture from salt-lake brines - Xunshuang Zhang; Yiming Hua; Mengyu Xie; Yihan Guo; Shilei Zhu; Yu He; Junxiang Wu; Shusen Chen; Zhou Song; Ya Nan Ye; Liangbin Li (Desalination, 2026)

Macroporous polyamidoxime particles with tunable cyclization functionalization via a swelling-restricted pore-locking preservation strategy for efficient uranium extraction from seawater - Junxiang Wu; Yu He; Xunshuang Zhang; Hongguang Mo; Yi Nan Wang; Shusen Chen; Zhou Song; Ya Nan Ye; Liangbin Li (Chemical Engineering Journal, 2026)

Development of combined mutagenesis strategy for enhanced eicosapentaenoic acid production in Schizochytrium sp. - Kai-Xin Liu; Qing Chen; Zi-lei Chen; Chun-Yong Jiang; Yang Wu; Xiu-Juan Li; Xiao-Le Liu; Min-Jie Cao; Bo Ren; Ya-Qiong Yang; Dong-Sheng Guo (Bioresource Technology, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

TRPV4/IP3R-1-mediated endothelial pyroptosis drives pulmonary microvascular endothelial permeability in endotoxin-induced acute lung injury - Shasha Liu; Shuan Dong; Lirong Gong; Jing Yang; Huayang Liu; Meiling Piao; Ya Wu; Huirong An; Li Zhang; Jianbo Yu (Inflammation Research, 2026)

Impact and evaluation of different temporal compositing strategies on the accuracy of tea plantation remote sensing mapping - Deng Zhi-Yong; Wu Guo-Hui; Liu Xiao-Jing; Yang Ya-Jie; Luo Jian; Zhang Hai-Yao; Du Xin-Lu; Li Ting; Wang Shan (International Journal of Remote Sensing, 2026)

A novel four-step strategy to discover processing-associated Q-markers from toxicity to bioactivity: Arisaema decipiens Schott (synonym: Arisaema rhizomatum C.E.C.Fisch.) as an example - Li Tang; Yu Yang; Xiao-hui Wu; Min Yan; Qiong Yang; Ya-li Wei (Natural Product Research, 2026)

Three new naphthoquinone-based meroterpenoids from Streptomyces sp. HBERC-16614 with antibacterial activities - Ya-Ni Zhang; Man-Li Liu; Fang Liu; Zhi-Gang Zhang; Zhao-Yuan Wu; Li-Qiao Shi; Zhong-Yi Wan; Yue-Ying Wang; Fei Zhang; Kai-Mei Wang; Wei Fang (Natural Product Research, 2026)

Coupling microbial electrosynthesis and chain elongation for simultaneous biomethane upgrading and carboxylate recovery: A tunable carbon valorization strategy - Kai-Kai Wu; Shu-tong Wu; Chuan Chen; Zi-Han Wang; Ya-Ru Wang; Li Zhao; Juan Tong; Fei Shen; De-Feng Xing; Nan-Qi Ren; Lei Zhao (Water Research, 2026)

Machine learning-driven 3D architecture of mineralized dolomite and potential rare earth element resources at Bayan Obo - Guoqiang Xue; Pengfei Lv; Qingyun Di; Jian Wang; Weiying Chen; Xin Wu; Ji’en Zhang; Ya Xu; Yonggang Zhao; Xianhua Li (Science Bulletin, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Efficient capture of Cs+ ions by two supertetrahedral cluster-based microporous metal chalcogenides in neutral and alkaline environments - Ya-Dong Wu; Lu Yang; Zhi-Hua Chen; Hai-Yan Sun; Chuan Lv; Xiao-Ying Huang; En-Chao Li; Mei-Ling Feng (Journal of Hazardous Materials, 2026)

Numerical and experimental study on the soot formation in methane multi-jet flames under microgravity - Wen-Jiao Wang; Kai-Ru Jin; Zhi-Hao Zheng; Hong-Qing Shi; Du Wang; Ling-Nan Wu; Ya-Wen Liu; Longfei Li; Jiayu Sun; Yu Cheng Liu; Zhen-Yu Tian (Fuel, 2026)

Pollutant-specific pathways linking gaseous air pollution to adolescent depressive symptoms: Direct and sleep-mediated effects in a population-based retrospective cohort study - Chun-Ji Lin; Po-Ya Chang; Yu-Ling Li; Chih-Da Wu; Chao-Ying Tu; Chih-Yi Wu; Szu-Ying Chen; Hung-Yi Chiou (Environmental Research, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

Molecular characterization of a novel partitivirus isolated from Fusarium solani, the causal agent of tobacco root rot - Xiao Wu; Ying Wang; Rui Guo; Ya Rong Wang; Si Jun Li; Xiang Ping Zhou; Jie Zhong; Yan Song Xiao; Tian Bo Liu (Archives of Virology, 2026)

Heteronemin suppresses chemoresistant oral squamous cell carcinoma cells through ROS-mediated apoptosis and cuproptosis-associated mitochondrial stress - Chiung-Wei Huang; Fan-Li Lin; Chun-Feng Chang; Hsiao-Hsuan Huang; Wan-Ju Wu; Hui-Min Chang; Mei-Ying Lin; Jue-Liang Hsu; Shih-Ya Hung; Chien Hsing Lee (Apoptosis, 2026)

Dysregulated KIF2A correlates with p53 expression pattern in breast cancer - Yun Hao; Si-Qin Ma; Ting Xu; Jia-Qi Wu; Rong Ma; Ya-Wen Wang; Jian-Li Wang (Molecular and Cellular Biochemistry, 2026)

High-efficiency micropropagation of Rhodiola species with concurrent bioactive compound validation - Cheng-cai Zhang; Xiang-tao Chen; Hong-yang Wang; Wei-wu Chen; Jiumi Ciwang; Xiao-yu Dai; Ya-fei Zhang; Qi Li; Sheng Wang; Ze-kun Zhang (In Vitro Cellular & Developmental Biology - Plant, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Urinary Fibroblast Growth Factor-23 and Soluble Alpha-Klotho in Cats with Chronic Kidney Disease - Wei-Che Chen; Wei-Li Hsu; Chao-Chin Chang; Pei-Shiue Jason Tsai; Vin-Cent Wu; Ya-Jane Lee (The Veterinary Journal, 2026)

Vegetation restoration enhances baseflow stability during hydrological droughts on the Loess Plateau, China - Ya Peng; Jiefeng Wu; Huaxia Yao; Yuliang Zhou; Jieru Yan; Guoqing Wang; Xuemei Li (Journal of Hydrology, 2026)

Freeze-casting polyamidoxime-based membrane adsorbents with synergistically enhanced mechanical properties and adsorption performance for uranium extraction from seawater - Yu He; Yanran Lu; Beibei Kang; Junxiang Wu; Xunshuang Zhang; Shilei Zhu; Zizhou Xu; Shusen Chen; Zhou Song; Ya Nan Ye; Liangbin Li (Journal of Environmental Chemical Engineering, 2026)

Potential structure-immunostimulatory activity relationship of Tartary buckwheat sprout pectic polysaccharides: Influences of molecular mass and esterification degree - Bo Li; Lin Zhang; Ding-Tao Wu; Qin Yuan; Shengpeng Wang; Mao-Ling Tan; Mei-Lin Feng; Yi-Chen Hu; Liang Zou; Zi-Peng Wang; Ya-Nan Cao; Jing-Wei Huang (Food Research International, 2026)

Impact of freezing storage on the structure integrity of pectin in Eureka lemons - Wen-Yu Gao; Ya-Xin Li; Na Ai; Sheng-Jiao Lei; Meng-Die Wu; Jun-Qian Wu (Food Chemistry, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Environmental heat and cold stress, thyrotropin abnormalities, and reduced fecundability in 14 million Chinese couples: A nationwide preconception cohort study - Xinghou He; Mengyao Li; Ying Yang; Xinyi Lv; Hongbing Xu; Bin Zhang; Long Wang; Chuanyu Zhao; Jiahui Liu; Yuan He; Jianbing Wu; Xinghua He; et al. (Environmental Research, 2026)

How sea-land breezes affect ozone in coastal cities: spatial and temporal patterns - Naixiu Sun; Ya-nan Wang; Yu Fei; Lin Wu; Yicheng Yang; Liwei Li; Xueling Yang; Hongjun Mao (Environmental Monitoring and Assessment, 2026)

Research on the Adaptive Response Mechanism of Bacterial Infection in Triplophysa siluroides - Yuanliang Duan; Ya Liu; Jun Ou; Feiyang Li; Xiaoyun Wu; Jianshen Lai; Jian Zhou; Mingjiang Song (Fishes, 2026)
Triplophysa siluroides, a unique species of plateau fish, holds significant economic value. However, its natural population has sharply declined due to overfishing and the construction of water conservancy projects. Investigating the various conditions necessary for its growth is a crucial prerequisite for successful artificial breeding. This study used Edwardsiella tarda as the pathogenic bacterium to determine the median lethal concentration following infection of T. siluroides, as well as to examine changes in tissues, organs, and gene expression. The study found that dead T. siluroides displayed symptoms such as abdominal distension, fluid accumulation, and a reddened anus, and the median lethal concentration of E. tarda for T. siluroides was calculated to be 1.00 × 106 CFU/mL. Following infection with E. tarda, the liver, intestine, gills, spleen, and kidneys exhibited varying degrees of lesions. Transcriptome sequencing identified a total of 54,667 genes. Compared to the blank control group, 192 genes were downregulated and 125 genes were upregulated in T. siluroides infected with E. tarda. In contrast, after infection with the poly(I:C) viral mimic, 225 genes were downregulated and 436 genes were upregulated. This study determined the median lethal concentration of E. tarda for T. siluroides via intraperitoneal injection under laboratory conditions. The results may contribute to disease prevention and control in the breeding of T. siluroides, as well as inform future risk assessments of infection in aquaculture water bodies.

Efficient combined use of electroacupuncture with ordered collagen scaffolds enhances the therapeutic efficacy of human spinal cord-derived neural progenitor cells therapy in spinal cord injury rats - Yunlong Zou; Weiwei Xue; Bo Guo; Lu Li; Yannan Zhao; Xianming Wu; Zhifeng Xiao; Qi Zhang; Dezun Ma; Xinhao Zhao; Bing Chen; He Shen; et al. (Science China Life Sciences, 2026)

Formal synthesis of (-)-warburganal and synthesis of (+)-isodrimenin - Xian-Hui Zhao; Liang Zhao; Yue-Cheng Wu; Ya-Jing Bian; Hui-Jing Li; Yan-Chao Wu (Natural Product Research, 2026)

Corrigendum to “Acanthoic acid protectsagainst ethanol-induced liver injury: Possible role of AMPK activation and IRAK4 inhibition” [Toxicol. Lett. 281 (2017) 127–138] - You-Li Yao; Xin Han; Jian Song; Jing Zhang; Ya-Mei Li; Li-Hua Lian; Yan-Ling Wu; Ji-Xing Nan (Toxicology Letters, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Ensemble learning: a study on the border inspection prediction model for high-risk products adulterated with Sudan Red in Taiwan - Li-Ya Wu; Wei-Chih Cheng; King-Fu Lin; Jia-Jhen Lee; Wen-Chou Lin; Hsu-Yang Lin; Chia-Yen Lu; Chih-Kang Chiang (Food Control, 2026)

Microglial membrane camouflaged biomimetic nanoformulation synergizing photothermal therapy and chemotherapy in glioblastoma - Ya Wang; Shuai Wu; Yunfan Li; Yuxin Huang; Kaiwen Bao; Ruyi Li; Renzheng Huan; Yuan Zhong; Li Zhu; Jianshu Li; Wei Wu; Haifeng Yang (Chemical Engineering Journal, 2026)

Cell-specific gene expression plasticity in response to hypoxia promotes high-altitude adaptive evolution - Wen-Tian Wei; Ze Yan; Hui Wu; Ming-Liang Zhou; Dong-Xin Mo; Xing Wan; Rui Ma; Mei-Ming Wu; Jia-Hui Huang; Ya-Jing Liu; Ji Yang; Meng-Hua Li (Science China Life Sciences, 2026)

Vertical Distribution of Phyllosphere Microbial Diversity in a Subtropical Forest: Increase From Canopy to Forest Floor - Yirui Zhang; Lingxiao Wu; Wenjie Li; Jie Wang; Qing Guo; Ya Gao; Renzhi Qin; Shuang Xing; Chang Liao; Chengjin Chu; Xian Yang (Environmental Microbiology, 2026)
The vertical structure of forests creates diverse habitats for microorganisms. Phyllosphere microbial communities, comprising leaf‐associated bacteria and fungi, are key components of forest ecosystems, yet their vertical distribution and assembly processes remain poorly understood. Here, we examined the diversity and composition of phyllosphere microbial communities across five vegetation layers (canopy, subcanopy, interlayer, shrub, and herb) in a subtropical forest in South China, and assessed the contributions of microclimates, host plant traits, and soil‐related factors. We found phyllosphere bacterial and fungal richness increased from the canopy to the forest floor, largely driven by microclimatic variation. Community composition shifted gradually along the vertical gradient, with adjacent layers being more similar. Soil microbial composition and properties explained a large proportion of variation in community composition, particularly for fungi, but their contributions were broadly consistent across vertical layers, with only a slight increase in the herb layer. In contrast, host traits became increasingly important for bacterial communities toward lower strata. These findings reveal clear vertical patterns in phyllosphere microbial diversity and composition, and suggest that distinct combinations of environmental filtering and host‐associated processes shape bacterial and fungal communities across forest strata.

Sparteine-type alkaloids with anti-tomato spotted wilt virus from the seeds of Lupinus angustifolius L. - Jian-Guo Tan; Cheng-Feng Liu; Li Wang; Xing-Ya Wu; Li-Hua Zhao; Xiao-Jiang Hao; Zhan-Xing Hu (Pesticide Biochemistry and Physiology, 2026)

Metamifop-induced human breast cancer cells proliferation: Revealing a proliferation mechanism distinct from 17β-estradiol - Jingjing Wu; Ya Zhou; Yu Wang; Junqi Zhu; Lu Lin; Huihua Tan; Shiling Liu; Yahui Li; Feng Zhao (Pesticide Biochemistry and Physiology, 2026)

Presymbiotic activation of karrikin signaling creates a permissive state for arbuscular mycorrhizal symbiosis by derepressing the NSP1–NSP2–SLR1 transcriptional complex in rice - Kai Hong; Xueying Yang; Yiqing Tan; Yonggang Liu; Qianwei Xia; Longjun Zeng; Linyuan Zou; Ke Wan; Ya Zhang; Shujing Kang; Tao Huang; Wanqing Lv; et al. (Molecular Plant, 2026)

Sediment transport mechanisms in sediment-starved subaqueous deltas: insights from storm-induced gravity flows - Chunye Hu; Fan Zhang; Jin Li; Xiaolei Liu; Fei Xing; Renzhi Li; Hao Wu; Heyu Yu; Ya Ping Wang (Journal of Hydrology, 2026)

High-yield exfoliation of micrometer-scale Ti3C2Tx assisted by silver nanowires for electrochemical sensing application - Xulin Li; Juan Wu; Yue Ma; Yuan Luo; Qian Long; Qiuzuo Shen; Junling Shao; Lingpu Jia; Huiming Li; Wenlong Liao; Ya Liu; Kunping Liu (Journal of Environmental Chemical Engineering, 2026)

Constructing diverse spinel/V2CTx heterostructures with tailored interfacial electron coupling for efficient oxygen evolution reaction - Li Dong; Shuang Li; Min Hu; Keke Li; Ya-Pan Wu; Xue-Qian Wu; Guangtong Hai; Cheng-Bin Zhong; Ru-an Chi; Dong-Sheng Li (Chemical Engineering Journal, 2026)

High-efficiency restoration of stone cultural relics via immobilized carbonic anhydrase on magnetic graphite oxide - Yaofeng Hu; Yifan Gui; Wei Li; Cuiling Gong; Ziqi Hou; Tong Shu; Ya Wu; Gen Lu; Longjiang Yu (Bioresource Technology, 2026)

Fine mapping and candidate gene dissection of the wheat powdery mildew resistance gene PmPBDH - Yuli Jin; Jiatong Li; Delin Li; Ningning Yu; Ya Zhao; Bo Wang; Jun Guo; Jiadong Zhang; Guantong Pan; Yaoxue Li; Yintao Dai; Nina Sun; et al. (Theoretical and Applied Genetics, 2026)

Exploring Empathic Responses to Others’ Positive and Negative Experiences: Insights from Empathy Subprocesses - Xiao Wu; Xue-Jing Lu; Li-Bo Zhang; Si-Rui Huo; Ya-Zhuo Kong; Li Hu (Neuroscience Bulletin, 2026)

LncRNA expression signature correlated with cuproptosis: prognostic implications and insights into immune microenvironment in ovarian cancer - Cong-Min Wang; Ya-li Hao; Xiao-Fei Li; Jian-lei Wu; Kai-Kai Hao; Fang Guo; Hai-Bo Zhang (Journal of Molecular Histology, 2026)

Photooxidation and ozonolysis of α-pinene and limonene mixtures: Mechanisms of secondary organic aerosol formation and cross-dimerization - Yingqi Zhao; Ya Zhao; Chong Wang; Yufeng Shao; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Ling Jiang; Xueming Yang (Journal of Environmental Sciences, 2026)

Potent dual-function of marine peptide N6NH2 and its D-enantiomer to combat MDR A. veronii infection in tilapia (GIFT, Oreochromis niloticus) - Ting Li; Na Yang; Da Teng; Ruoyu Mao; Ya Hao; Huihui Han; Yankang Wu; Xiumin Wang; Jianhua Wang (Fish & Shellfish Immunology, 2026)

Research on the texture of canned bamboo shoots preserved under ultra-high pressure: Based on the molecular structure of pectin and cell wall integrity - Xiaohua Sun; Dan Chen; Ziyi Zhan; Ya Wang; Liangru Wu; Jinlai Yang; Jiong Zheng; Li Dong; Xiaosong Hu; Fusheng Zhang (Food and Bioproducts Processing, 2026)

From strong to switchable adhesion: Gecko-inspired design strategies and practical applications - Changlin Shen; Weimin Heng; Chunxiao Wu; Xinrui Hou; Yichen Fan; Ya Li; Yekun Han; Qi’ao Yang; Lei Wang; Zhilong Peng; Shaohua Chen (Chemical Engineering Journal, 2026)

Integrated transcriptomic and metabolomic analyses reveal the molecular adaptive mechanisms of Schizopygopsis chengi baoxingensis under acute heat stress - Hangyu Lin; Xiaoyun Wu; Ya Liu; Jun Ou; Luyun Ni; Feiyang Li; Jiansheng Lai; Quan Gong; Jue Lin; MingJiang Song (Journal of Thermal Biology, 2026)

A triple-functional NiCo2S4/Mn0.2Cd0.8S/Cu7S4 heterojunction for superior photothermal-assisted photocatalytic H2 evolution - Yan Xiong; Ya Li; Ya-Nan Wu; Qun-Zeng Huang (Journal of Environmental Chemical Engineering, 2026)

Comprehensive review of fat replacers utilized in sausages: Classification, advantages, and applications - Pei Yang; Yuwei Liu; Ya Liu; Huan Guo; Dingtao Wu; Renyou Gan; Zhihua Li; Yina Huang; Hong Gao (Food Chemistry, 2026)

Effects of geographical origin, variety, harvest season, and their interactions on stable isotopes and multi-elements in tea - Xiao-Li Wang; Bo-Wen Zhang; Ya-Nan Wu; Yan-Bo Hao; Xue-Jiao Chen; He-Yuan Jiang; Hong-Yan Liu (Food Control, 2026)

U-shaped association between outdoor artificial light at night exposure and metabolic syndrome in Chinese youth: Findings from a nationally representative study - Wen-xin Ge; Zhao-huan Gui; Zhi-Yong Zou; Li-qing Yao; Wen-wen Bao; Le-bing Wang; Li-xin Hu; Zheng-ge Jin; Wan-xin Wu; Jun Ma; Ying-Hua Ma; Ya-jun Chen (Environmental Pollution, 2026)

Targeted photodynamic therapy for multispecies dental biofilms using liposome encapsulated p-Toluquinone - Chen Liang; Yongli Li; Zuan-Tao Lin; Zhilong Wang; Ya He; Yan Dong; Zihan Ran; Sophia Zhang; Ying Zhao; Songling Wang; Mei X. Wu (Chemical Engineering Journal, 2026)

A phytoalexin-inspired, natural product-based marine antifouling coating with synergistic active antimicrobial and passive anti-adhesive performances - Liang Ma; Xing-Yu Lei; Qi Xu; Ya-Fu Li; Yu-Hao Li; Peng-Fei Chen; Jian-Cai Chen; Hui-Jing Li; Yan-Chao Wu (Chemical Engineering Journal, 2026)

Revealing Multi-Stage Thermal Imprints: Evolution Model and Dominant Drivers in Cambrian Qiongzhusi Shale, Sichuan Basin - Dandan Wang; Zhenxue Jiang; Majia Zheng; Dadong Liu; Xianglu Tang; Zhuo Li; Ya Wu; Wenyi Chen; Huan Miao; Zijun Tang; Tianye Li (Journal of Earth Science, 2026)

Genetic origins and climate‐induced erosion in economically important Asian walnuts - Peng‐Zhen Fan; Guang‐Fu Zhu; Moses C. Wambulwa; Richard I. Milne; Zeng‐Yuan Wu; Ya‐Huang Luo; Robabeh Shahi Shavvon; Alistair S. Jump; Debabrata Maity; Lian‐Ming Gao; Hai‐Ling Qi; Hong‐Yu Wu; et al. (Conservation Biology, 2026)
The global climate is undergoing unprecedented changes, posing significant threats to species persistence. However, the spatiotemporal impacts on genetic diversity remain poorly understood, hindering species conservation and management. Walnuts, generally referred to as Juglans regia and J. sigillata , are economically vital in Asia, but little is known about their genetic origins and how the species will be affected by future climate change. Using 31 microsatellites, we genotyped 5282 individuals from 233 populations of walnuts in Asia. We assessed genetic diversity patterns and demographic history and investigated potential future genetic erosion risks. Genetic diversity of walnuts was high in the Himalaya and Hengduan Mountains. The 2 species diverged during the Pleistocene (around 1.41 Ma BP), and J. regia contained 2 genetic groups (JR1 and JR2). The JR2 group had the lowest diversity and likely arrived in northern China around 9.77 ka BP, perhaps via human transport. The Western Himalaya likely served both as a glacial refugium and the center of origin for J. regia , and the Eastern Himalaya appears to have been the refugium for J. sigillata . The 2 species appear to have hybridized in the Central Himalaya and the Sichuan basin and surroundings, forming two distinct hybrid zones. Our results indicate that genetic diversity will be reduced by up to 9.03% due to range loss under future climate change and dramatic genetic structure turnover in the Himalaya and Hengduan Mountains. In situ conservation in the Himalaya is essential for safeguarding genetic diversity and adaptive potential in Asian walnuts, while ex situ preservation of genetically unique wild germplasm, coupled with its integration into breeding programs, will enhance climate resilience. The findings advance our understanding of the origin of Asian walnuts and how future climatic change may affect their genetic diversity, offering a model for conservation and breeding strategies in other tree species facing similar threats.

Exploring the impacts of flavonoid compounds on escitalopram metabolism: a combined in vitro and in vivo study - Hailun Xia; Jun Wu; Haoxin Fu; Peiqi Wang; Ruibin Li; Lu Cao; Ya-nan Liu; Lu Shi; Ren-ai Xu (Molecular Diversity, 2026)

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

Three new exquisitely preserved haplolepideous mosses from the mid-Cretaceous of Kachin, Myanmar - Ya Li; Yong-Dong Wang; Peng-Cheng Wu; Lwin Mar Saing; Chun-Xiang Li; Qiang Wang (Review of Palaeobotany and Palynology, 2026)

Cascading effects of cross-year droughts on flow-sediment dynamics across distinct drought types - Jiefeng Wu; Jian-yun Zhang; Huaxia Yao; Ya Peng; Yuliang Zhou; Mei Chen; Xuemei Li; Jie Wang; Guoqing Wang (Journal of Hydrology, 2026)

Multi-scale evaluation of six fused evapotranspiration products over mainland China: Accuracy, consistency and uncertainty - Dayang Wang; Dagang Wang; Shaobo Liu; Zequn Lin; Ya Huang; Xiaohang Ma; Mengjiao Wu; Yanyu Ma; Jialu Zhu; B. Larry Li (Journal of Hydrology, 2026)

A metal-immuno photosensitizer strategy: Iridium(III)-zidovudine conjugate triggering sequential organelle stress and synergizing with PD-L1 inhibitor in oral squamous cell carcinoma - Yi-Ling Li; Peng Wang; Wu-Ya Zhang; Rui Zhou; Jia-Ying Zhou; Jia-Wen Chen; Jia-Yin Wu; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Bright and stable green-emitting quantum dots with universal surface modifiability for diagnostic probes - Ning Li; Dexia Zhou; Ya Liu; Ziming Zhou; Zhaobing Tang; Siqi Jia; Ruili Wu; Huaibin Shen; Yanbing Lv; Lin Song Li (Chemical Engineering Journal, 2026)

Glycogen Synthase Kinase-3β Inhibition Ameliorates Synaptic and Mitochondrial Dysfunction in a Sporadic Alzheimer’s Disease–Like Model - Ya-Han Wang; Peng-Li Ding; Hao Qin; Kai-Xin Zhang; Jin-Wen Ge; Da-Hua Wu; Le Xie; Kun Liang (Molecular Neurobiology, 2026)

Screening and In Vivo Validation of Key Genes Involved in Myelin Damage in Alzheimer’s Disease - Hai-Tao Li; Ji-Wei Zhang; Bo-Wen Li; Hong-Yun Wu; Jin-Wen Ge; Da-Hua Wu; Quan-Lin Zhao; Ya-Han Wang (Molecular Neurobiology, 2026)

Biological safety assessment of dissolved aluminum ions in coastal seawater: acute toxicity effects on Pacific whiteleg shrimp (Litopenaeus vannamei) Post-larvae - Pei-Hsuan Wu; Yen-Kung Hsieh; Tsang-Hsieh Hung; Wei-Shan Chou; Ya-Rung Wu; Ping Chen; Jin-Li Yu; Chao-Kai Kang (Ecotoxicology, 2026)

Recombinant GnRH6-kisspeptin-CRM197 vaccine inhibits reproductive function in male rats and dogs - Yanyun Zhu; Mengxian Li; Xiangyang Jiang; Dongyuan Fu; Zhihao Pan; Zhuoya Wu; Kejian Han; Ya Liu; Yunsheng Li; Tong Yu; Kaiyuan Ji; Mengling Peng; et al. (The Veterinary Journal, 2025)

Petrogenesis of Triassic intermediate-felsic intrusions from three skarn tungsten deposits in the East Kunlun Orogenic Belt, NW China: Evidence from zircon U Pb geochronology, petrochemistry, and Hf isotopic characteristics - Yan Tan; Jin-Xiang Li; Fang Xu; Yan-Qian Yang; De-Xin Zhang; Hua-Liang Lai; Sheng-Qiang Ma; Shun-Long Yang; Yi-Jun Yang; Chen Wu; Ya-Hui Yue; Chao Wang; et al. (Lithos, 2025)

Recovering carbon fibers from waste carbon fiber reinforced polymer composites via electrified Joule heating-assisted pyrolysis - Ming-xin Xu; Jie Yang; Xiang-xi Meng; Jun-ping Zhang; Yi-ye Lu; Ya-chang Wu; Wei Li; Qiang Lu (Journal of Environmental Sciences, 2025)

Comparative studies of the NOx impacts on the photooxidation mechanisms of isomeric monoterpenes of β-pinene and limonene - Yingqi Zhao; Zhaoyan Zhang; Ya Zhao; Chong Wang; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Ling Jiang; Xueming Yang (Journal of Environmental Sciences, 2025)

Innovative cellulose-based porous matrix loaded with carvacrol microemulsion for sustainable mango preservation - Linyun Mou; Jianlong Li; Ya Lu; Lin Wu; Guijun Bu; Juan Li; Ganpeng Li (International Journal of Food Microbiology, 2025)

The variation of the East Asian summer monsoon on multi-centennial scale during 8.3–2.9 ka BP - Chao-Jun Chen; Ya-Xi Dong; Yao Wu; Jian Zhang; Hai-Bo Wang; Yan-Xia Xue; Wen-Jun Sun; Man-Ping Xie; Hai Cheng; Jun-Yun Li; Ming-Qiang Liang; Ting-Yong Li (Global and Planetary Change, 2025)

Assembling L-malic acid and Co-MOF in ultrasonically synthesized pectin/gelatin films: A versatile food preservation composite film - Xu Han; Wen-Shuo Xue; Shang Wu; Qi Zhang; Wei-Teng You; Zi-heng Wang; Han Jiang; Ya-Li Zhang; Yuan-Yuan Li (Food Chemistry, 2025)

Study on the effects of representative spice polyphenols on the in vitro digestive properties of tilapia myofibrillar protein and its mechanism of action: based on physical and chemical properties and enzyme activity - Zirui Fu; Jun Li; Ya Wei; Jianwei Cen; Huan Xiang; Xiao Hu; Chunsheng Li; Yanyan Wu; Shengjun Chen; Yongqiang Zhao; Hui Huang; Shuxian Hao (Food Chemistry, 2025)

Associations of children's urinary metals with blood RNA N6-methyladenosine and 2′-O-methyladenosine - Carolyn Gigot; Ya Li; Haotian Wu; Guadalupe Estrada-Gutierrez; Mari Cruz Tolentino; Alejandra Cantoral; Julio Landero; Martha M. Téllez-Rojo; Robert O. Wright; Yinsheng Wang; Allison Kupsco (Environmental Research, 2025)

Engineering fast-response thermal control for dynamic gene expression design in Halomonas - Jian-Lian Wu; Ya-Ge Xiao; Bao-Wen Liu; Ling-Fan Tian; Ling-Fei Tian; Yu-Xi Li; Jia-Wen Peng; Hai-Fan Zhu; You-Yang Wang; Zhe-Yi Kuang; Jiang-Jie Tian; Shuai Zheng; et al. (Chemical Engineering Journal, 2025)

A facile and universal ligand exchange strategy enables sequential surface functionalization of quantum dots for high quality in vivo imaging - Xue-Hui Shi; Zhendong Zhu; Changlin Shen; Ya Li; Zhuang Qian; Yonghao Wu; Huifeng Chen; Qing-Qing Ye; Chaojie Hu; Yifan Song; Lei Wang; Zhimou Yang; et al. (Chemical Engineering Journal, 2025)

Development of novel melatonin-isatin hybrids as multifunctional agents for Alzheimer’s disease - Ying-Ying Zhong; Jun‑Ze Deng; Qin Wang; Li Chen; Zi-Hang Yang; Ya-Mei Zhang; Lu‑Yi Zhou; Yi-Ran Li; Jia-Qiang Wu; Xiao-Qin Wang (Molecular Diversity, 2025)

Research on the Mechanism of Complex Water-flooded Layers and Well Logging Evaluation Methods in the M Oilfield - Wen-Yuan He; Ya-Dong Wu; Li-Xiang Feng; Chang-Xi Li; Jin-Bin Wan; Guo-Hui Ni (Applied Geophysics, 2025)

Identification of cDNA-AFLP fragments associated with the B chromosome from different developmental stages of maize anthers - Cheng-Hong Li; Pei-Hsuan Wu; Ya-Ming Cheng (Chromosome Research, 2025)

High-performance dynamic radiative regulation via controllable macroscopic materials modulation - Ya Huang; Xueke Wu; Siming Zhao; Baoshun Wang; Zhuojing Zhao; Di Gao; Run Li; Yunrui Li; Fei Wang; Fan Lan; Yanlong Zhao; Rufan Zhang (Science Bulletin, 2025)

Self-sustained Bio-Fenton system driven by Shewanella oneidensis for efficient degradation of persistent organic pollutants under oxygen-limited conditions - Yang-Yang Fan; Xuan Yao; Zhi-Yong Li; Xin-Yu Yang; Ming-Juan Zou; Zi-Yi Zhang; Kun Wu; Ting Huang; Ya-Ning Sun; Xiang Xiao (Journal of Hazardous Materials, 2025)

Volatile organic compounds in various workplaces and during commutes in a Chinese city: occurrence and health risks for different occupations - Jin-Long Mai; Yi Yang; Yuan Zeng; Song Liu; Zhen-Shan Huang; Jia-Hua Wu; Ya-Jing Li; She-Jun Chen (Environmental Research, 2025)

Experimental and numerical study on the fire resistance behavior of steel truss girder structure in double deck suspension bridges - Zongxing Zhang; Yuxuan Xu; Yuwei Li; Wei Chen; Jihong Ye; Mingchun Wu; Ya Ni; Jian Jiang (Engineering Structures, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

Functional miRNA-mRNA Regulatory Modules in the Head Kidney of Pelteobagrus vachellii in Response to Aeromonas veronii Infection - Feiyang Li; Xiaoyun Wu; Yeyu Chen; Qiaolin Zou; Pengcheng Li; Mingjiang Song; Quan Gong; Ya Liu; Jiansheng Lai; Luyun Ni; Jun Wang (Fishes, 2025)
Aeromonas veronii is a major pathogen threatening freshwater aquaculture, yet the molecular mechanisms of Pelteobagrus vachellii’s immune response to this infection remain unclear. This study integrated histopathology, mRNA-seq and small RNA-seq to investigate P. vachellii’s response to A. veronii at 48 h post-challenge. Histopathologically, infection induced gill epithelial detachment, hepatocyte swelling with cytoplasmic vacuolation, and melanomacrophage centers (MMCs) in the mid-kidney (histological assessment of the head kidney was not feasible due to sampling limitations associated with its small size). Transcriptomic analysis identified 1210 differentially expressed genes (DEGs) in the head kidney (819 downregulated, 391 upregulated), significantly enriched in 11 immune pathways (e.g., NF-κB, Th17 cell differentiation, Complement and coagulation cascades), with key immune genes (e.g., IL-1β, TCRα, CCL4) upregulated. Gene Set Enrichment Analysis (GSEA) revealed activation of the proteasome, ribosome and oxidative phosphorylation pathways, and suppression of the autophagy-animal, FoxO and AMPK pathways. Small RNA-seq identified 544 known and 958 novel miRNAs in the head kidney, with 42 downregulated and 36 upregulated differentially expressed miRNAs (DE miRNAs). The miRNA-mRNA network showed that DE miRNAs (e.g., miR-101-y/z, miR-132-z, miR-3167-y) negatively regulated immune-related target genes (IL-1R1, IRF4, IκBα) in core immune pathways. Collectively, this study clarifies the pathological and miRNA-mRNA regulatory modules of P. vachellii head kidney against A. veronii infection, providing valuable information that enables the further analyses of the defense mechanisms of P. vachellii against A. veronii infection.

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

Deep eutectic solvent-mediated green synthesis of phosphorylated biomass adsorbents for high-efficient uranium removal from uranium tailings wastewater - Ya Wei Yang; Jie Liu; Jing Huang; Cheng Rong Zhang; Sai Jin Xiao; Xin Xin Shao; Han Wu; Li Zhang (Journal of Environmental Chemical Engineering, 2025)

Bifunctional Fe3O4@mTiO2@MXene-NH2 prepared by homogeneous wrapped-in-net method for the detection and simultaneous photocatalytic degradation of fluoroquinolones in water - Xulin Li; Yue Ma; Juan Wu; Yuan Luo; Qian Long; Yixuan Kuang; Junling Shao; Lingpu Jia; Huiming Li; Wenlong Liao; Kunping Liu; Ya Liu (Journal of Environmental Chemical Engineering, 2025)

Design and characterization of AgC nanocomposite frameworks in porous silicon anodes for high-performance solid-state batteries - Baoguo Zhang; Lin Wu; Xiaoyu Yang; Jingwang Li; Zefeng Yuan; Zihao Dang; Rongsheng Chen; Ying Liu; Ya Hu (Chemical Engineering Journal, 2025)

Morphological Analysis of the Intestine in Yangtze Sturgeon (Acipenser dabryanus) During Development - Luyun Ni; Xiaoyun Wu; Feiyang Li; Qiaolin Zou; Jun Du; Jiansheng Lai; Ya Liu (Fishes, 2025)
This study aimed to investigate the histological features of the intestine of Acipenser dabryanus from 1 to 15 months of age via HE staining, AB-PAS staining, scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The intestine of A. dabryanus comprises the duodenum, spiral valve intestine, and rectum. With age, the duodenal diameter and mucosal/muscular layer thickness increased, the spiral valve intestine’s mucosa thickened and protrusions formed networks, and the rectal diameter enlarged. Abundant mucus cells, predominantly type IV, were found in the duodenum, spiral valve intestine, and rectum of A. dabryanus at different ages by AB-PAS staining. Our study confirmed the presence of ciliated columnar cells (with ‘9 + 2’ cilia structure) with orderly arranged cilia at their apices in the mucosal epithelium of A. dabryanus’s duodenum, spiral valve intestine, and rectum for the first time, as shown by SEM and TEM. The presence of spiral valves and ciliated columnar cells in the intestinal structure of A. dabryanus highlights its unique features and evolutionary significance. These findings highlight A. dabryanus’s unique intestinal features and evolutionary significance, providing a basis for scientific feed formulation and enhancing our understanding of the histological characteristics of the sturgeon intestine.

Acetamiprid mediates cognitive dysfunction through the gut-brain axis: Synaptic damage and immune-mediated blood-brain barrier dysfunction - Bing Wu; Xue-yan Tian; Wen-si Ni; Hao-Xuan Gao; Yu-wen Wang; Ling-he Zhang; Yu-bin Li; Yan-ling Lv; Ya-nan Song; Yu-cheng Yan; Xiao-zhe Geng; Yi-man Li; et al. (Journal of Hazardous Materials, 2025)

Adsorption and coarsening of gold nanoparticles in iron (oxyhydr)oxides lead to high-grade gold mineralization - Feng-Xia Huang; Ya-Fei Wu; Katy Evans; Anthony E. Williams-Jones; Xin-Fu Zhao; Yong Wei; Wei Feng; Jian-Wei Li (Geochimica et Cosmochimica Acta, 2025)

Sustainable extraction of Lycium barbarum leaf Phenolics using deep eutectic solvents: Optimization, bioactivity, and functional food potential - Yi-Long Ma; Qian-Lan Wu; Lu Jian; Xin Guo; Jing Li; Tian-Le Mao; Zhi Li; Ya-Fang Shang; Kiran Thakur; Shao-Hua Yang; Zhao-Jun Wei (Food Chemistry, 2025)

Quality changes and deterioration mechanisms during frozen storage of starching tilapia fillets based on quality characteristics, protein properties and microstructure analysis - Qingqing Wu; Huan Xiang; Shuxian Hao; Jianwei Cen; Shengjun Chen; Yongqiang Zhao; Chunsheng Li; Hui Huang; Ya Wei (Food Chemistry, 2025)

Loperamide-induced constipation is associated with excessive accumulation of bile acids and cholesterol in the liver of mice; attenuation by hesperidin - Jiahui Li; Dan Bi; Ya Nie; Huijuan Wu; Yuting Lei; Siping Yu; Hedong Rong; Yanhong Yang; Zili Lei (Food and Chemical Toxicology, 2025)

Remobilization of Ni in framboidal pyrite within sulfide nodules in Early Cambrian nickeliferous black shales - Xu-Yang Liu; Ya-Fei Wu; Daniel D. Gregory; Katy Evans; Anthony E. Williams-Jones; Wen Zhang; Mei-Fu Zhou; Jian-Wei Li (Chemical Geology, 2025)

Anthropogenic effects on Δ3-carene photooxidation: Different oxidants induce significant changes of secondary organic aerosol formation mechanisms - Ya Zhao; Chong Wang; Yingqi Zhao; Yufeng Shao; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Ling Jiang; Xueming Yang (Atmospheric Environment, 2025)

The Impact of Culturally Relevant Nutrition Education on Healthy Eating Behaviors in Chinese American Elementary School Students: A Mixed-Methods Study - Ya Gao; Eric Wang; Chumin Wu; David Kim; Xinyu Cai; Danying Li (Journal of Nutrition Education and Behavior, 2025)

Ag/Ag2S plasmonic heterostructure promotes piezoelectric photocatalytic activity of BiFeO3 nanofibers for degradation of ciprofloxacin and energy conversion - Chucheng Zhou; Jinshan Wei; Jing Xu; Tianle Wu; Ji Zhou; Ya-yun Li (Journal of Environmental Sciences, 2025)

PDA-Au-nanocluster-loaded polyacrylamide alginate hydrogels for dural repair and functional recovery - Dehong Wu; Yuanwen Zou; Weina Zhang; Xiaoming Wang; Zhongbing Huang; Wenhao Li; Ya Li; Jiang Wu; Guangfu Yin (Chemical Engineering Journal, 2025)

TISCalling: leveraging machine learning to identify translational initiation sites in plants and viruses - Ming-Ren Yen; Ya-Ru Li; Chia-Yi Cheng; Ting-Ying Wu; Ming-Jung Liu (Plant Molecular Biology, 2025)

Effect of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel on physicochemical, texture and sensory properties of low-fat yoghurt - Ya-Hui Yu; Luo-Bang Wu; Long-Qing Li; Ming-Yu Jin; Xiaozhen Liu; Xiangying Yu; Fengyuan Liu; Yuting Li; Lin Li; Jing-Kun Yan (Food Chemistry, 2025)

Effects of mono- and di-glycerides/phospholipids (MDG/PL) on the bioavailability of lutein and DHA in rats: more effective for lutein - Shu-zhen Huang; Huan-huan Yin; Fang Tian; Liang Wang; Wen-jing Wu; Xiang Li; Yanrong Zhao; Xiao-ya Wang; Yun Li; Megan Terp; Ying-yi Mao; Jin-yao Chen (Food Bioscience, 2025)

Bioinspired copper-doped covalent organic polymers with laccase-mimicking activity for on-site monitoring of thiram in fruit and vegetable samples - Ya Di Shi; Meng Ping Wang; Han Wu; Sai Jin Xiao; Zi Yang Yue; Ding Zhong Yuan; Xin Xin Shao; Feng Tao Yu; Li Zhang (Analytica Chimica Acta, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Three new polyketide metabolites from the endophytic fungus Trichoderma protrudens of Hibiscus tiliaceus - Yan-Mei Wu; Jing-Ya Mo; Yong-Yan Mei; Quan Liu; Yuan-Yuan Huang; Bei Zhou; Yi-Hang Li; Yan-Chun Wu; Jing-Quan Yuan (Phytochemistry Letters, 2025)

Evolution patterns, driving mechanisms, and ecological indicative effects of 730 lakes water color in the Yangtze River Basin (1984–2023) - Qi Chen; Zhijing Li; Zhongwu Jin; Shiming Yao; Yinjun Zhou; Huali Wu; Ya Liu; Guoshuang Zhang; Yujiao Liu; Xuhai Yang; Yisen Wang; Zhaoxi Liu; et al. (Journal of Hydrology, 2025)

Green construction and digestive properties of Fe (II) and quercetin double-loaded delivery system by wampee polysaccharide and its application - Juan-li Fang; Fu-lan Hu; Ya-qin Wu; Tao Liu; Peng-peng Sun; Yuan-yuan Ren (Food Chemistry, 2025)

Greenness, nighttime light, and couple fecundability: A national cohort study between 2014 and 2020 - Mengyao Li; Xinghou He; Bin Zhang; Hongbing Xu; Jianbin Wu; Xuyang Shan; Ya Zhang; Huiying Xu; Hongguang Zhang; Yuan He; Yan Fang; Zuoqi Peng; et al. (Environmental Research, 2025)

Reusable solid catalyst with self-adaptive surface: Dedicated to efficient, racemization-resistant and catalyst-contamination-free depolymerization of poly(L-lactide) - Ya-Juan Wu; Guo-Qiang Tian; Yi-Ying Zhang; Hang Li; Si-Chong Chen; Gang Wu; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

TSPO activation ameliorates maternal immune activation induced PV interneuron deficits via BDNF/TrkB signaling - Ming-Jie Mao; Hui-Ling Yu; Qing-Zhen Liu; Ya-Zhou Wen; Ming Jiang; Hong-Mei Yuan; Hua-Bei Zeng; Li-Dong Zhang; Shan-Wu Feng (Psychopharmacology, 2025)

Hydrogen peroxide regulated split-type electrochemiluminescence sensing platform for non-invasive detection of gastric cancer-associated D-amino acids - Juan Li; Ming-Chun Lai; Ya-Meng Zhong; Ya-Ling Chen; Na Wu; Wei Chen; Hua-Ping Peng (Analytica Chimica Acta, 2025)

T-2 toxin-induced splenic injury by disrupting the gut microbiota–spleen axis via promoting IL-6/JAK/STAT1 signaling-mediated inflammation and apoptosis and its mitigation by elemental nano-selenium - Meng Liu; Xue-Wu Li; Hua Sun; Yi-Qin Yan; Zhi-Yuan Xia; Alainaa Refaie; Ni-Ya Zhang; Shuai Wang; Chen Tan; Lv-Hui Sun (Archives of Toxicology, 2025)

COP1 Overexpression Attenuates Nociceptive Behaviors and Neuroinflammation in Cancer-Induced Bone Pain by Suppressing c/EBPβ - Dan-Yang Li; Lin Liu; Shao-Jie Gao; Dai-Qiang Liu; Long-Qing Zhang; Jia-Yi Wu; Fan-He Song; Xin-Yi Dai; Ya-Qun Zhou; Wei Mei (Journal of Neuroimmune Pharmacology, 2025)

Association of long-term ozone exposure with the incidence and progression of hypertension, diabetes, and chronic kidney disease: A national retrospective cohort study - Yu-Ling Li; Po-Ya Chang; Ting-Wu Chuang; Yi-Chen Hsieh; Bo-Sian Wang; Szu-Ying Chen; Hung-Yi Chiou (Science of The Total Environment, 2025)

Discovery and configurations assignment of Ile/Leu-containing cyclic peptides with cytotoxic activity, Reniochpeptins A–D, from the marine sponge Reniochalina sp. - Shuai-Shuai Zhang; Zong-Mei Wu; Ying Wu; Ya-Jun Zeng; Yuan-Yuan Zhang; Xin-Li Lin; Si Zhang; Kai-Xuan Zhan; Hou-Wen Lin; Shu-Ping Wang (Phytochemistry, 2025)

Relationship between starch granule-associated proteins and in vitro digestibility of buckwheat starches: From the perspective of gelatinization degree - Jin Du; Zhen Lu; Kai Cheng; Changfeng Li; Hao Wu; Bin Xu; Jian-Ya Qian (Food Chemistry, 2025)

Evaluate the sensitivity of rapeseed lodging under low light：A field study on the biomechanics of stem and root lodging in rapeseed (Brassica napus L.) - Yue Hu; Hafiz Hassan Javed; Li Liu; Nadiyah M. Alabdallah; Kamran Ghaffor; Ya-long Liu; Yu-qin Luo; Faiza Gulzar; Xiao Peng; Yong-cheng Wu (Field Crops Research, 2025)

Polygonatum cyrtonema Hua polysaccharide alleviates ulcerative colitis via gut microbiota-independent modulation of inflammatory immune response - Jin-Yang Shi; Yong-Jian Wang; Qian-Wen Bao; Ya-Min Qin; Pei-Pei Li; Qiao-Qiao Wu; Cheng-Kai Xia; De-Ling Wu; Song-Zi Xie (Carbohydrate Polymers, 2025)

A chemiluminescence immunoassay for detection of Toxoplasma gondii antibody in porcine based on GRA6 and SAG1 - Ran Wu; Ya-Fei Song; Yanlong Gu; Jiang Li; Zhipeng Niu; Dong-Hui Zhou (Veterinary Parasitology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Preconception maternal hyperoxia exposure causes cardiac insufficiency through induction of mitochondrial toxicity in mice offspring - Dan Chen; Zhi-xuan Xing; Sheng-peng Li; Tao Lu; Jia-xin Wang; Ya-xian Wu; Qing-feng Pang (Reproductive Toxicology, 2025)

Anti-neuroinflammatory terpenes from Magnolia grandiflora - Ding-Xun Wu; Jue Yang; Li-Hua Chen; Shuang-Yu Xu; Jun Jin; Ya-Nan Li; Xiao-Jiang Hao; Chun-Mao Yuan (Phytochemistry, 2025)

Effects of isoprene on the ozonolysis of Δ3-carene and β-caryophyllene: Mechanisms of secondary organic aerosol formation and cross-dimerization - Zhaoyan Zhang; Yingqi Zhao; Ya Zhao; Xiangyu Zang; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Xueming Yang; Ling Jiang (Journal of Environmental Sciences, 2025)

Unlocking the chemical basis of fermented golden pompano (Trachinotus ovatus) inoculated with indigenous Bacillus subtilis: Focus on the role of lipid oxidation on volatile flavor formation - Huifang Wang; Yanyan Wu; Shengjun Chen; Yongqiang Zhao; Chunsheng Li; Huan Xiang; Di Wang; Ya Wei; Yueqi Wang (Food Chemistry, 2025)

Active immunization with a novel recombinant GnRH vaccine inhibits reproductive function in male goats - Moyan Di; Xinbao Gong; Yanyun Zhu; Shibao Guo; Zhihao Pan; Mengxian Li; Zhuoya Wu; Wei Zhang; Xuelan Liu; Ya Liu; Yunsheng Li; Jian Li; et al. (Domestic Animal Endocrinology, 2025)

S-scheme heterojunction of WO3/metal-covalent organic frameworks for artificial photosynthetic CO2 reduction - Liang Fang; Li-Wen Bai; Di Wu; Hong-Tu Che; Yanxia Jiang; Ya Wang; Hong Dong; Feng-Ming Zhang (Chemical Engineering Journal, 2025)

A functional slurry additive for robust interphase and stabilized high-voltage nickel-rich cathodes in lithium-ion batteries - Xuanting Wu; Junwei Feng; Said Amzil; Meilan Peng; Wenlu Zhai; Min Li; Xingchen Liu; Ya-Jun Cheng; Yonggao Xia (Chemical Engineering Journal, 2025)

Correction to: Deep plastid phylogeographic divergence of beaked hickory (Carya sinensis) calls for transboundary conservation in a biodiversity hotspot - Xiao-Yu Song; Moses C. Wambulwa; Richard Milne; Winnie W. Mambo; Zeng-Yuan Wu; Zhong-Hu Li; Ya-Huang Luo; Dinh Duy Vu; Jie Cai; Guang-Fu Zhu; Zhi-Peng Li; Lei Cai; et al. (Tree Genetics & Genomes, 2025)

Identification and characterization of anthocyanins’ composition and regulatory genes involved in anthocyanins biosynthesis in water dropwort (Oenanthe javanica) - Kai Feng; Nan Sun; Ya-Qing Bian; Wu-Di Rui; Ya-Jie Yan; Zhi-Yuan Yang; Jia-Lu Liu; Zi-Qi Zhou; Shu-Ping Zhao; Peng Wu; Liang-Jun Li (Planta, 2025)

Botryorhodine J, a new anti-MRSA depsidone isolated from endophytic fungus Alternaria alternata Pas11 - Wen-Yuan Li; Cheng-Cheng Hu; Jin-Hai Liu; Heng-Jie Wang; Ling-Pan Lu; Min Qiao; Ya-Ling Jiang; Rui Wu (Natural Product Research, 2025)

Large language models for diabetes training: a prospective study - Haoxuan Li; Zehua Jiang; Zhouyu Guan; Yuqian Bao; Yuexing Liu; Tingting Hu; Jiajia Li; Ruhan Liu; Liang Wu; Di Cheng; Hongwei Ji; Yong Wang; et al. (Science Bulletin, 2025)

The Arabidopsis heterotrimeric G protein α subunit binds to and inhibits the inward rectifying potassium channel KAT1 - Jiang-Fan Guo; Hui Zhou; Zhuo-Ran Hu; Ya-Lan Yang; Wen-Bin Wang; Yan-Ru Zhang; Xue Li; Nuerkaimaier Mulati; Ying-Xin Li; Lu Wu; Yu Long; Jun-Min He (Plant Science, 2025)

Insertional mutagenesis of AIDA or CYP720B1 in the green alga Chlamydomonas reinhardtii confers copper(II) tolerance and increased biomass - Ya Li; Lin Jiang; Chuang Xu; Suhui Wang; Yunyao Qian; Yiqiong Wu; Chenyu Miao; Zhouzhou Dong; Liang Wang (Journal of Hazardous Materials, 2025)

Effects of mixed exposure to PFAS on adolescent non-alcoholic fatty liver disease: Integrating evidence from human cohorts, toxicogenomics, and animal models to uncover mechanisms and potential target sites - Xiushuai Du; Dan-Lin Li; Xueming Xu; Yitian Wu; Zhiyuan Du; Gang Liang; Yue-Zu Li; Ya-Jie Zheng; Yu Qin; Kelei Qian; Jing Xu; Liping Gao; et al. (Journal of Hazardous Materials, 2025)

A framework for the construction of effective landscape ecological network with integrating hydrological connectivity: A case study in Dongjiang River Basin, China - Xin Jiang; Zhi-Yun Jiang; Zhen-Ya Li; Jie Su; Li-Na Tang; Meng-Di Wu; Yi-Jia Wang (Journal of Environmental Management, 2025)

Effect of polystyrene micro/nanoplastics on PCBs removal in constructed wetlands planted with Myriophyllum aquaticum - Shuang Wang; Jun Liu; Rongjie Kang; Ya Liu; Xuan Zhao; LiTing Wang; Zhaocheng Wu; Yan Lei; Jibing Li (Environmental Research, 2025)

A new exceptionally preserved corystosperm wood from the Jurassic of East Asia - Zikun Jiang; Ning Tian; Yongdong Wang; Fangyu Li; Junling Pei; Dieter Uhl; Ya Li; Hao Wu; Zhenguo Ning; Ruiying Hao (Science China Earth Sciences, 2025)

Incorporating Genetic Diversity to Optimize the Plant Conservation Network in the Third Pole - Moses C. Wambulwa; Guang‐Fu Zhu; Ya‐Huang Luo; Zeng‐Yuan Wu; Jim Provan; Marc W. Cadotte; Alistair S. Jump; Francis N. Wachira; Lian‐Ming Gao; Ting‐Shuang Yi; Jie Cai; Hong Wang; et al. (Global Change Biology, 2025)
Climate change poses a significant threat to the survival of many species. Although protected areas can slow down biodiversity loss, they often lack systematic planning and do not integrate genetic diversity. Genetic diversity is a key prerequisite for species survival and the ability to tolerate new conditions. Using population genetic and distribution data from 96 plant species in the Third Pole (encompassing the Tibetan Plateau and adjacent mountains), we mapped patterns of genetic diversity, projected climate‐driven range dynamics and future genetic erosion, and designed an optimal conservation framework for the region. We identified several patches of high haplotype diversity ( H D ), with a relatively high number of haplotypes in southeastern Third Pole. Regression models revealed that climate and topography have interacted to shape patterns of genetic diversity, with latitude and precipitation being the best predictors for H D of cpDNA and nrDNA, respectively. Ecological niche modeling predicted an approximate 43 km northwestward and 86 m upward shift in suitable habitats under future climate scenarios, likely leading to a significant loss of up to 13.19% and 15.49% of cpDNA and nrDNA genetic diversity, respectively. Alarmingly, 71.20% of the newly identified conservation priority areas fall outside of the existing protected areas and planned National Park Clusters. Therefore, we recommend expanding the network by 2.02 × 10 5 km 2 (5.91%) in the Third Pole, increasing the total conserved area to 1.36 × 10 6 km 2 (39.93%) to effectively preserve the evolutionary potential of plants. This study represents an innovative attempt to incorporate genetic diversity into biodiversity conservation efforts.

KCNJ15 inhibits chemical-induced lung carcinogenesis and progression through GNB1 mediated Hippo pathway - Hong-qiang Chen; Na Wang; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Ya-wen Li; Shuang-wu Deng; Zi-yuan Zhou; Wen-bin Liu (Toxicology, 2025)

Innovative coupling pathway for second- and third-generation biomass: Efficient L-lactate synthesis from xylose and C1 compounds - Ya Wu; Gen Lu; Ruiqi Zeng; Zeyang Li; Xin Xu; Yifan Gui; Chonghao Guo; Lizhen Deng; Yutong Bie; Derui Zhang; Yuxin He; Yuyang He; et al. (Chemical Engineering Journal, 2025)

Membrane transport engineering for efficient yeast biomanufacturing - Xin-Yue Li; Ming-Hai Zhou; Du-Wen Zeng; Yi-Fan Zhu; Feng-Li Zhang; Sha Liao; Ya-Chao Fan; Xin-Qing Zhao; Lin Zhang; Feng-Wu Bai (Bioresource Technology, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Investigation of Feeding Effects and Environmental Impact of Fish-Feed Quality: Evidence from Crucian Carp Feeding Experiments - Jiayin Wang; Ran Wu; Jianhua Wang; Jiangtao Guo; Ya Zhang; Nanbing Shi; Jinxing Gu; Yibing Han; Xinyi Guo; Zhe Yu; Guoxi Li; Zhenjiang Yang (Fishes, 2025)
The effects of three types of feed, purchased from online stores and having similar prices, on the growth performance and culture environment of crucian carp (Carassius auratus) were studied in this experiment, which aimed to provide a reference for the evaluation and selection of fish feed. The results showed that feeding different feeds had a significant effect on crucian carp, and that the growth-promoting effect of HD feed (feed produced by Haida Company Limited) was significantly better than that of the other two feeds. For example, the weight gain rate (WGR) of fish in the HD group was 47.1% higher than that in the LD group (p

NAGK regulates the onset of puberty in female mice - Wei Zhang; Ping Qin; Mengxian Li; Zhihao Pan; Zhuoya Wu; Yanyun Zhu; Ya Liu; Yunsheng Li; Fugui Fang (Theriogenology, 2025)

Genome-wide characterization and comparative transcriptomics unravel CpMADS47 as a positive regulator during fruit ripening and softening in Chinese cherry - Tai Tian; Shiqing Yin; Fengting Huang; Longqiang Feng; Yan Ma; Hao Wang; Jing Zhang; Wen He; Yuanxiu Lin; Yunting Zhang; Mengyao Li; Zhiwei Wu; et al. (Postharvest Biology and Technology, 2025)

Effects of UV-A irradiation and microbial fermentation on the physicochemical, microstructure and functional properties of okara - Ya-Ting Lei; Fan-Bing Meng; Xiao-Lei Jiao; Yuan-Mou Tang; Qi-Jun Wu; Yun-Cheng Li (Food Research International, 2025)

Effect of excitation voltage in a magnetically induced electric field on the physicochemical, structural and functional properties of citrus pectin - Ya-Hui Yu; Xiaozhen Liu; Luo-Bang Wu; Xiangying Yu; Ming-Yu Jin; Long-Qing Li; Fengyuan Liu; Yuting Li; Lin Li; Bing Li; Jing-Kun Yan (Food Chemistry, 2025)

The dynamic changes in physicochemical properties, functionalities, and gel properties of the starch-konjac gum mixture during the melting process: Based on three typical melting temperatures of DSC - Chen Zhang; Xin-Yu Li; Jing-Jing Li; Yu-Yan Zhang; Chu-Yun Wu; Zhi-Juan Wang; Ling-Zhi Zhang; Chunsen Wu; Qiao-Quan Liu; Jian-Ya Qian (Food Hydrocolloids, 2025)

Prospective LCA towards achieving carbon neutrality goals: Framework application and challenges - Ya-Xi Fang; Pei-Ze Wu; Sha Chen; Yu Li; Shu-Fen Cui; Jin-Xing Zhu; Hai-Zhou Cao; Ke-Jun Jiang; Ling Zhong (Environmental Impact Assessment Review, 2025)

Efficient capture of gaseous, aqueous iodine, near-sunlight white light emission and iodine sensing in 12-connected and [Pb6]-cluster based MOFs - Ya-Nan Yu; Wei-Min Ma; Jia-Xin Wu; Qian Zhang; Jie Zhou; Ke-Ke Jiang; Dan-Dan Wang; Yong-Kang Li; Yang-Min Ma; Zheng Yin (Chemical Engineering Journal, 2025)

Mechanism, diffusion, and kinetics characteristics of nitrocellulose denitrification revealed by DFT and MD - Shen Li; Zhong-Xin Liu; Shi-Ying Li; Ya-Jun Ding; Zhong-Liang Xiao; Jie Zhou; Xiao-Qing Wu; Hong-Lei Fan; Zheng-Hong Luo; Xi-Bao Zhang (Chemical Engineering Journal, 2025)

Structural analysis and accelerating wound healing function of a novel galactosylated glycosaminoglycan from the snail Helix lucorum - Ya Li; Xingzi Wang; Jiangyan Chen; Luyun Sun; Debing Pu; Lisha Lin; Lan Luo; Xi Gong; Junxue Pu; Mingyi Wu (Carbohydrate Polymers, 2025)

Kv3.1 Interaction with UBR5 Is Required for Chronic Inflammatory Pain - Ying Zeng; Meng-Lan Sun; Di Liu; Yue Huang; Shan Xie; Ya-Xuan Zhao; Zi-Xuan Wu; Ya Liu; Gan Ma; Ling Xie; Yu-Tao Dang; Ling-Yun Hao; et al. (Molecular Neurobiology, 2025)

Dual emission chiral carbon dots as fluorescent probe for fast chiral recognition of tryptophan enantiomers - Qi Wu; Yuan Chen; Yan-Li Wang; Ji-Ying Song; Hai-Tao Lv; Ya-Ming Sun (Analytica Chimica Acta, 2025)

Dune activity history in China's east dunefields over the past millennium - Zhipeng Wu; Jinchang Li; Caixia Zhang; Ya Zhou (Journal of Quaternary Science, 2025)
Dune activity encompasses both activation and dune stabilization processes, with the former potentially threatening the sustainability of global ecosystems and human societies. Research on historical dune activity has raised concern among environmental scientists and serves as a foundation for assessing recent and future changes in arid and semi‐arid ecosystems. Disagreements related to the causes of historical dune activation persist because of the lack of a more detailed dune activity history for China's east dunefields. Based on stratigraphic evidence, historical documents and archaeological discoveries in the Mu Us and Horqin dunefields, this study presents a detailed dune activity history as well as the forcing mechanisms for China's east dunefields as a whole over the past millennium. The results revealed that two episodes of extensive dune activation (from 800 to 940 ce and from 1300 to 2000 ce ) occurred in China's east dunefields, accounting for 69% of the past millennium. The proportions of extensive dune activation driven by a cold and dry climate (from 800 to 940 ce and from 1300 to 1730 ce ), strong human activity (from 1900 to 2000 ce ) and their combined impacts (from 1730 to 1900 ce ) were approximately 68%, 12% and 20%, respectively. Thus, China's east dunefields were in a state of extensive dune activation for most of the past millennium, and most extensive dune activation was driven by climate. Local or sporadic dune activation occurred from 940 to 1300 ce and since 2000 ce in China's east dunefields, which was caused by strong human activity.

Silica-coated nano zero-valent iron as a slow-release electron donor for sustained enhancement of aerobic denitrification in oligotrophic source water: Performance and mechanism - Tianhua Wu; Jiaxin Li; Ruihua Cao; Xiaojie Chen; Jingyi Wang; Ya Cheng; Baoshan Wang; Tinglin Huang; Gang Wen (Science of The Total Environment, 2024)

Comparative life cycle assessment of PBAT from fossil-based and second-generation generation bio-based feedstocks - Chenkai Luo; Ya Zhou; Zhitong Chen; Xinchao Bian; Ning Chen; Junjie Li; Yufeng Wu; Zhifeng Yang (Science of The Total Environment, 2024)

The correlation between single and mixed trace elements exposure in systemic lupus erythematosus: A case-control study - Rong-Gui Huang; Kai-Di Li; Hong Wu; Yi-Yu Wang; Ya Xu; Xue Jin; Yu-Jie Du; Yi-Yuan Wang; Jing Wang; Zhang-Wei Lu; Bao-Zhu Li (Journal of Trace Elements in Medicine and Biology, 2024)

Deep learning-assisted detection of psychoactive water pollutants using behavioral profiling of zebrafish embryos - Ya Zhu; Lan Li; Shaokui Yi; Rui Hu; Jianjun Wu; Jinqian Xu; Junguang Xu; Qinnan Zhu; Shijia Cen; Yuxuan Yuan; Da Sun; Waqas Ahmad; et al. (Journal of Hazardous Materials, 2024)

Insights into bioaerosol contamination in the process of mineralized refuse mining: Microbial aerosolization behavior and potential pathogenicity - Ya-nan Wang; Qingzhao Wang; Yahui Li; Bingpeng Wang; Huawei Wang; Yingjie Sun; Jun Wu; Weihua Li; Rongxing Bian; Liejun Chen (Journal of Hazardous Materials, 2024)

Per- and poly-fluoroalkyl substances (PFAS) accelerate biological aging mediated by increased C-reactive protein - Zongxi Zhao; Jiayan Zhou; Anye Shi; Jingyi Wang; Hongzheng Li; Xiangjun Yin; Jialiang Gao; Ying Wu; Jinlin Li; Ya Xuan Sun; Hao Yan; Yige Li; et al. (Journal of Hazardous Materials, 2024)

Coupling of anthropogenic activities and natural factors on dissolved organic matter: Insights from coastal urban rivers in southern China - Ya Wang; Yafeng Zhang; Shi Tang; Yongjin Liang; Renren Wu; Penghui Li (Journal of Environmental Chemical Engineering, 2024)

Influence of intruding organic acids on the leaching dynamics of heavy metals in stabilized MSWI fly ash from landfills under various percolation conditions - Yinkai Wu; Weihua Li; Junquan Yin; Yuan Gao; Qingjian Zhang; Yingjie Sun; Weijie Gao; Jing Lu; Qifei Huang; Rongxing Bian; Ya-nan Wang; Huawei Wang (Journal of Environmental Chemical Engineering, 2024)

Selective production of phenol from the end-of-life wind turbine blade through catalytic pyrolysis - Ji-hong Li; Hao Jiang; Wei-wei Chen; Ya-chang Wu; Ming-xin Xu; Jin-yi Di; Wei Li; Qiang Lu (Fuel, 2024)

Unraveling anti-aging mystery of green tea in C. elegans: Chemical truth and multiple mechanisms - Jia-ping Ke; Jia-Yi Li; Zi Yang; Hao-Yue Wu; Jing-Ya Yu; Yi Yang; Chen-Hui Chen; Peng Zhou; Fang Hua; Wei Wang; Fenglin Hu; Gang-Xiu Chu; et al. (Food Chemistry, 2024)

A non-contact quantitative risk assessment framework for translational highway landslides: Integration of InSAR, geophysical inversion, and numerical simulation - Qianyou Fan; Shuangcheng Zhang; Yufen Niu; Xiaolong Zeng; Jinzhao Si; Xuhao Li; Wenhui Wu; Jianwen Jiang; Sichan Qiu; Ya Kang (Engineering Geology, 2024)

Deep plastid phylogeographic divergence of beaked hickory (Carya sinensis) calls for transboundary conservation in a biodiversity hotspot - Xiao-Yu Song; Moses C. Wambulwa; Richard Milne; Winnie W. Mambo; Zeng-Yuan Wu; Zhong-Hu Li; Ya-Huang Luo; Dinh Duy Vu; Jie Cai; Guang-Fu Zhu; Zhi-Peng Li; Lei Cai; et al. (Tree Genetics & Genomes, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Nanoparticle attachment promotes nugget effect of Au-rich metallic melts in hydrothermal ore deposits - Gao-Hua Fan; Jian-Wei Li; Ya-Fei Wu; Si-Yu Hu; Xiao-Dong Deng; Hao-Yang Zhou; Zhan-Ke Li; Yan Liu (Contributions to Mineralogy and Petrology, 2024)

Amelioration activity of the high bioaccessible chrysanthemum (Gongju) phenolics on alcohol-induced oxidative injury in AML-12 cells - Yi-Long Ma; Zhi Li; Zheng-Fang Wu; Qian-Lan Wu; Xin Guo; Ya-Fang Shang; Kiran Thakur; Zhao-Jun Wei (Food Chemistry, 2024)

Sensitizing sorafenib to hepatocellular carcinoma with dual-targeted and pH-responsive nanodrugs via overcoming the hypoxia tumor microenvironment - Zhe Li; Jinshuai Lan; Ya Wu; Lixia Chen; Donghao Gu; Liyan Sun; Siqi Yang; Yi Shen; Tong Zhang; Yue Ding (Chemical Engineering Journal, 2024)

Effects of NOx and NH3 on the secondary organic aerosol formation from α-pinene photooxidation - Yingqi Zhao; Zhaoyan Zhang; Ya Zhao; Chong Wang; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Ling Jiang; Xueming Yang (Atmospheric Environment, 2024)

Acute Recruitment of VTA Dopamine Neurons by mPOA Esr1+ Neurons to Facilitate Consummatory Male Mating Actions - Zhuo-Lei Jiao; Min Zhang; Ya-Nan Wu; Shuai-Shuai Li; Meng-Tong Gao; Wen Zhang; Xiao-Hong Xu (Neuroscience Bulletin, 2024)

Trichoderma harzianum promoting chrysanthemum cutting rooting and reshaping microbial communities in endophytic and rhizosphere environments - Ya-Jie Wu; Murad Muhammad; Yu Jiao; Xiu Chen; Hai-Long Wang; Chun-Mei Lu; Xiao-Ming Wang; Guo-Xing Zhu; Kai-Qing Liu; Yue Zhang; Zi-Chao Liu; Zhi-Xing Chen; et al. (Applied Soil Ecology, 2024)

Nrf2 deficiency exacerbated pulmonary pyroptosis in maternal hypoxia-induced intrauterine growth restriction offspring mice - Dan Chen; Ling-yun Man; Ying-ying Wang; Wei-ying Zhu; Hui-min Zhao; Sheng-peng Li; Yan-li Zhang; Shuai-chao Li; Ya-xian Wu; Ling-Ai; Qing-feng Pang (Reproductive Toxicology, 2024)

Thalamic Nucleus Reuniens Glutamatergic Neurons Mediate Colorectal Visceral Pain in Mice via 5-HT2B Receptors - Di Li; Han Du; Shu-Ting Qu; Jing-Lai Wu; Yong-Chang Li; Qi-Ya Xu; Xia Chen; Xiao-Xuan Dai; Ji-Tian Xu; Qian Wang; Guang-Yin Xu (Neuroscience Bulletin, 2024)
Irritable bowel syndrome (IBS) is a common functional bowel disorder characterized by abdominal pain and visceral hypersensitivity. Reducing visceral hypersensitivity is the key to effectively relieving abdominal pain in IBS. Increasing evidence has confirmed that the thalamic nucleus reuniens (Re) and 5-hydroxytryptamine (5-HT) neurotransmitter system play an important role in the development of colorectal visceral pain, whereas the exact mechanisms remain largely unclear. In this study, we found that high expression of the 5-HT 2B receptors in the Re glutamatergic neurons promoted colorectal visceral pain. Specifically, we found that neonatal maternal deprivation (NMD) mice exhibited visceral hyperalgesia and enhanced spontaneous synaptic transmission in the Re brain region. Colorectal distension (CRD) stimulation induced a large amount of c-Fos expression in the Re brain region of NMD mice, predominantly in glutamatergic neurons. Furthermore, optogenetic manipulation of glutamatergic neuronal activity in the Re altered colorectal visceral pain responses in CON and NMD mice. In addition, we demonstrated that 5-HT 2B receptor expression on the Re glutamatergic neurons was upregulated and ultimately promoted colorectal visceral pain in NMD mice. These findings suggest a critical role of the 5HT 2B receptors on the Re glutamatergic neurons in the regulation of colorectal visceral pain.

Paleozoic orogenic gold mineralization from metamorphism of volcanic sequences in the North Qinling terrane (central China): Insights from the Yindongpo gold deposit in the Tongbai area - Ming-Chun Chai; Jian-Wei Li; Ya-Fei Wu; Xiao-Ping Xia; Huai-Yu He; Wei Fu (Mineralium Deposita, 2024)

Selenium nanoparticles alleviates cadmium induced hepatotoxicity by inhibiting ferroptosis and oxidative stress in vivo and in vitro - Chunyan Shao; Tongwang Luo; Shujie Wang; Zhuoyue Li; Xiaoqiang Yu; Ya Wu; Sheng Jiang; Bin Zhou; Quanjiang Song; Shengzhe Song; Xiaodu Wang; Houhui Song (Chemosphere, 2024)

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

Influence of Chinese herbal plants on greenhouse gas emissions from pig manure composting and fermentation - Ya-jun Duan; Hong-sheng Wu; Guang-yao Chen; Feng-yi Hu; Yan-hui Li; Zhen-wei Li; Jin-he Chi; Dong-ming Lu; Xiao-ming Gu; Ming-chun Di (International Biodeterioration & Biodegradation, 2024)

In vitro simulated digestion and fermentation characteristics of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel - Ya-Hui Yu; Luo-Bang Wu; Xiaozhen Liu; Li-Chao Zhao; Long-Qing Li; Ming-Yu Jin; Xiangying Yu; Fengyuan Liu; Yuting Li; Lin Li; Jing-Kun Yan (Food Chemistry, 2024)

Associations among global long interspersed nuclear element-1 DNA methylation, metal exposure, and chronic kidney disease - Yu-Mei Hsueh; Mei-Chieh Chen; Ying-Chin Lin; Chih-Yin Wu; Horng-Sheng Shiue; Sheng-Lun Hsu; Hsi-Hsien Chen; Ya-Li Huang (Archives of Toxicology, 2024)

In-situ observations of wave- and current-supported fluid mud dynamics on a hyperturbid macrotidal mudflat - Mingliang Li; Dezhi Chen; Hao Wu; Jieping Tang; Yiyi Zhang; Feng Luo; Fugang Gou; Xulong Gong; Ya Ping Wang (Frontiers in Marine Science, 2024)
Wave- and current-supported fluid mud on gently sloped continental shelves represents a type of sediment gravity flow capable of rapidly transporting substantial sediment over short periods, significantly contributing to coastal geomorphic evolution. To investigate the dynamics of intertidal fluid mud events, in-situ observations were conducted from May 9 to May 18, 2017, using a seabed tripod system at the lower intertidal flat of the central Jiangsu coast, China. Fluid mud was observed following a medium wind-wave event, with a maximum significant wave height of 0.42 m. The liquefied seabed, loosened by liquefaction, facilitated bed erosion and sediment resuspension. Fluid mud layers, with mean suspended sediment concentrations (SSCs) exceeding 10 g/L, periodically formed during high slack tide, early flood, and late ebb phases. These layers varied in thickness from 4 cm to 20 cm and exhibited strong stratification caused by suspended sediment. Fluid mud disappeared when the bottom turbulence kinetic energy exceeded a threshold of 0.00045 m²/s² due to an increase in current velocity. The downslope movement of intertidal fluid mud was estimated using a theoretical buoyancy-friction model and validated by observed offshore-directed velocity jets at 0.1 m above the seabed during high slack tide phases. Additionally, onshore winds favored fluid mud formation during early flood phases, while offshore winds favored it during late ebb phases. These observations suggest that fluid mud can form on intertidal flats under conditions where tidal flows and winds align, contributing to a deeper understanding of the formation mechanisms of shallow gravity flows and the improvement of sediment transport models.

PKM2/Hif-1α signal suppression involved in therapeutics of pulmonary fibrosis with microcystin-RR but not with pirfenidone - Yan Ren; Jie Wang; Wen-wen Guo; Jing-wen Chen; Li-zhi Xu; Zhi-wei Wu; Ya-ping Wang (Toxicon, 2024)

Spatiotemporal variations of plankton communities in different water bodies of the Yellow River: Structural characteristics, biogeographic patterns, environmental responses, and community assembly - Meiling Yi; Lingqi Li; Haoran Li; Chang Liu; Ya Deng; Zi Wu; Yang Li (Journal of Hydrology, 2024)

Efficient gold scavenging by iron sulfide colloids in an epizonal orogenic gold deposit - Ya-Fei Wu; Katy Evans; Anthony E. Williams-Jones; Denis Fougerouse; Kirsten Rempel; Paul Guagliardo; Jian-Wei Li (Geochimica et Cosmochimica Acta, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Enhanced separation flux and compressive strength for oil-water separation by adding sodium lignosulphonate - Hui Jiang; Jun Li; Chao Wu; Zi-wei Xiong; Jia-wei Ding; Hui-fen Su; Ya-hui Li; Wen-bo Luo; Liu-jie Yuan; Si-yi Lv; Lu-xiang Wang; De-qiang Li (Chemical Engineering Journal, 2024)

Development of the near-infrared fluorescence probe for detection of ONOO− and its application in vitro and vivo - Ya-Jing Shang; Yuan-Yuan Li; Jia-Ling Hu; Yi-Ru Wang; Sheng-Tao Li; Xing-Hu Wu; Ai-Hong Zhang; Yu-Wei Tan; Ting Liang; Xiao-Bo Zhu; Yan-Fei Kang (Analytica Chimica Acta, 2024)

Saccharopolyspora mangrovi sp. nov., a novel mangrove soil actinobacterium with distinct metabolic potential revealed by comparative genomic analysis - Yi-Ting Lu; Yi-Yi Wu; Ya-Nan Li; Wei-Yi Zheng; Wen-Zheng Liu (Archives of Microbiology, 2024)

Are vacuolar dynamics crucial factors for plant cell division and differentiation? - Ya-Nan Wu; Jin-Yu Lu; Sha Li; Yan Zhang (Plant Science, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

Anti-inflammatory activity of organic acids from the seeds of Phaseolus lunatus L. - Kun Li; Jin-hui Bian; Heng Wu; Ya-lan Wang; Yun-jia Feng; Jia Nie; Na Chen; Han Yu; Wan Li; Yu-zhu Tan; Guang-hua Lu (Phytochemistry Letters, 2024)

Fabrication of Au-polydopamine blackspheres-loaded PLLA-(silk fibroin) scaffold with photothermal conversion in NIR-II biowindows for deep nerve regeneration - Chenshi Hu; Xiaohui Li; Zhongbing Huang; Jiaying Li; Juan Wang; Ximing Pu; Ya Li; Jiang Wu; Guangfu Yin (Chemical Engineering Journal, 2024)

Chemical constituents from the leaves of Fraxinus hubeiensis, an endemic plant from China - Li-Min Gong; Hong-Xia Tang; Ya-Jie Li; Rui-Ding Wen; Xin-Yi Liu; Yu-Wen Deng; Qing-Lai Wu; Zhi-Feng Zhang; Xu-Dong Zhou; Wei Wang (Biochemical Systematics and Ecology, 2024)

Neglected function of gastrin to reduce feeding in Siberian sturgeon (Acipenser baerii) via cholecystokinin receptor B - Shupeng Zhang; Yongpei Lu; Yanling Liu; Mei Wang; Shaoqi Xu; Ya Li; Hongwei Wu; Qaolin Pei; Lei Yang; Lu Lu; Yixiao Xiong; Youlian Liu; et al. (Fish Physiology and Biochemistry, 2024)

Identification of volatile compounds and their bioactivities from unpolar fraction of Alpinia oxyphylla Miq. and mining key genes of nootkatone biosynthesis - Fapetu Kemi Busayo; Jin-Ling Yang; Xu-Po Ding; Ya-Li Wang; Cui-Juan Gai; Fei Wu; Hao-Fu Dai; Wen-Li Mei; Hui-Qin Chen (Natural Product Research, 2024)

Co-pyrolysis of sewage sludge and phosphate tailings: Synergistically enhancing heavy metal immobilization and phosphorus availability - Ya Xiao; Tinggui Yan; Pin Yao; Weixue Xiang; Yunqi Wu; Jiang Li (Waste Management, 2024)

Antihypertensive treatment during pregnancy induces long-term changes in gut microbiota and the behaviors of the attention deficit hyperactivity disorder offspring - Hong-Bao Li; Meng-Lu Xu; Wen-Jie Xia; Yuan-Yuan Dong; Bo Peng; Qing Su; Xiao-Min Wang; Jia-Yue Yu; Ya-Nan Gao; Jun-Zhe Wu; Meng-Yue Xu; Jin-Bao Yang; et al. (Toxicology and Applied Pharmacology, 2024)

Corrigendum to “Theoretical and numerical studies of the coupled Bjerknes and buoyancy effects on the dynamics of an underwater explosion bubble near a free surface” [Ocean Eng. 297, April 2024] - Lei Wang; Yun-Feng Zhang; Hao Li; Ya-Guang Sui; Ke Wu; Da-Min Zhang; Wen-Hao Yao (Ocean Engineering, 2024)

Remobilization of carbon in the lithospheric mantle during decratonization - Ya-Dong Wu; Jin-Hui Yang; Vadim S. Kamenetsky; Hao Wang; Xiao-Guang Li (Lithos, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Esterified wheat bran: Physicochemical properties, structure and quality improvement of Chinese steamed bread during refrigerated storage - Hua Li; Qingfeng Wu; Yanyan Guo; Ya Dai; Yali Ping; Zhenzhen Chen; Beibei Zhao (Food Chemistry, 2024)

Modifying duck myofibrillar proteins using sodium bicarbonate under cold plasma treatment: Impact on the conformation, emulsification, and rheological properties - Shengqi Jiang; Chunjie Yang; Rong Bai; Ziwei Li; Linlu Zhang; Ya Chen; Xiang Ye; Siying Wang; Hao Jiang; Wu Ding (Food Hydrocolloids, 2024)

IRE1α: from the function to the potential therapeutic target in atherosclerosis - Zheng-Yang Zhou; Li Wu; Yi-Fan Liu; Mu-Yao Tang; Jing-Yi Tang; Ya-Qian Deng; Lei Liu; Bin-Bin Nie; Zi-Kai Zou; Liang Huang (Molecular and Cellular Biochemistry, 2024)

Advanced “turn-on” colorimetric uranium platform based on the enhanced nanozyme activity of a donor-acceptor structured covalent organic framework - Sai Jin Xiao; Jing Huang; An Ting Qiu; Guang Zhou Liu; Li Zhang; Ting Wu; Ya Di Shi; Jian-Ding Qiu (Analytica Chimica Acta, 2024)

Spatial-temporal constraints for surface soil moisture mapping using Sentinel-1 and Sentinel-2 data over agricultural regions - ZHOU Ya'nan; WANG Binyao; ZHU Weiwei; FENG Li; HE Qisheng; ZHANG Xin; WU Tianjun; YAN Na'na (Computers and Electronics in Agriculture, 2024)

Viologen-based ionic conjugated mesoporous polymer as the electron conveyer for efficient polysulfide trapping and conversion - Hai-Yang Li; Zhong-Shan Li; Gang-Hao Qiu; Rou-Rou Zhang; Ya-Rui Wang; Feng Wang; Ren-Wu Huang; Xiao-Fei Liu; Shuang-Quan Zang (Science Bulletin, 2024)

Theoretical and numerical studies of the coupled Bjerknes and buoyancy effects on the dynamics of an underwater explosion bubble near a free surface - Lei Wang; Yun-Feng Zhang; Hao Li; Ya-Guang Sui; Ke Wu; Da-Min Zhang; Wen-Hao Yao (Ocean Engineering, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Hsa-miR-877-5p Expression in Acute Ischemic Stroke Based on Bioinformatics Analysis and Clinical Validation - Si-Shuo Zhang; Ji-Wei Zhang; Kai-Xin Zhang; Wen-Qiang Cui; Hong-Wei Zhi; Hai-Tao Li; Hong-Yun Wu; Ya-Han Wang (Molecular Neurobiology, 2024)

Sources and seasonal variations of nitrate in the coastal multiple-aquifer groundwater of Beihai, southern China - Ya Wu; Huaiqing Liu; Hongxin Zhang; Qinghua Li (Journal of Contaminant Hydrology, 2024)

Enzyme-immobilized nanoclay hydrogel simultaneously reduces inflammation and scar deposition to treat spinal cord injury - Tong Wu; Yajun Li; Zhiyan Wu; Ziqiang Wang; Ya Li; Ke Jian; Chaoyong He; Can Zhang; Liyang Shi; Jianwu Dai (Chemical Engineering Journal, 2024)

Smartphone-assisted self-powered dual-mode biosensor designed on binary 3D DNA Walkers mediated CRISPR/Cas12a system - Jinyue Shi; Peiyuan Li; Yumei Huang; YeYu Wu; Jiawen Wu; Ke-Jing Huang; Xuecai Tan; Yu Ya (Chemical Engineering Journal, 2024)

Clinical and genetic architecture of a large cohort with auditory neuropathy - Hongyang Wang; Liping Guan; Xiaonan Wu; Jing Guan; Jin Li; Nan Li; Kaili Wu; Ya Gao; Dan Bing; Jianguo Zhang; Lan Lan; Tao Shi; et al. (Human Genetics, 2024)
Auditory neuropathy (AN) is a unique type of language developmental disorder, with no precise rate of genetic contribution that has been deciphered in a large cohort. In a retrospective cohort of 311 patients with AN, pathogenic and likely pathogenic variants of 23 genes were identified in 98 patients (31.5% in 311 patients), and 14 genes were mutated in two or more patients. Among subgroups of patients with AN, the prevalence of pathogenic and likely pathogenic variants was 54.4% and 56.2% in trios and families, while 22.9% in the cases with proband-only; 45.7% and 25.6% in the infant and non-infant group; and 33.7% and 0% in the bilateral and unilateral AN cases. Most of the OTOF gene (96.6%, 28/29) could only be identified in the infant group, while the AIFM1 gene could only be identified in the non-infant group; other genes such as ATP1A3 and OPA1 were identified in both infant and non-infant groups. In conclusion, genes distribution of AN, with the most common genes being OTOF and AIFM1 , is totally different from other sensorineural hearing loss. The subgroups with different onset ages showed different genetic spectrums, so did bilateral and unilateral groups and sporadic and familial or trio groups.

In vitro digestibility and hepato-protective potential of Lophatherum gracile Brongn. leave extract - Yi-Long Ma; Zheng-Fang Wu; Zhi Li; Yue Wang; Ya-Fang Shang; Kiran Thakur; Zhao-Jun Wei (Food Chemistry, 2024)

Effects of NO and SO2 on the secondary organic aerosol formation from isoprene photooxidation - Zhaoyan Zhang; Yingqi Zhao; Ya Zhao; Xiangyu Zang; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Xueming Yang; Ling Jiang (Atmospheric Environment, 2024)

A new cyclohexenone derivative from phomopsis sp. XM-01 - Cheng-Yao Wang; Dong Gan; Chen-Zhe Li; Li Zhu; Xiao-Ran Zhang; Ya-Ni Li; Xiu-Hong Wu; Hao Zhou; Le Cai (Natural Product Research, 2024)

Se-(Methyl)-selenocysteine ameliorates blood-brain barrier disruption of focal cerebral ischemia mice via ferroptosis inhibition and tight junction upregulation in an Akt/GSK3β-dependent manner - Yuxiang Fei; Tao Li; Ruoyu Wu; Xuejiao Xu; Sheng Hu; Ya Yang; Chenchen Jin; Wenlian Tang; Xu Zhang; Qianming Du; Chao Liu (Psychopharmacology, 2024)

Potential protective effects of sodium butyrate on glycinin-induced oxidative stress, inflammatory response, and growth inhibition in Cyprinus carpio - Deng-Lai Li; Si-Ying Liu; Rui Zhu; Si-Tong Meng; Yin-Tao Wang; Zhi-Yong Yang; Liang Li; Xiao-Fang Wei; Guo-Jun Shang; Hao-Tong Wang; Zi-Hui Qu; Ya-Nan Quan; et al. (Fish Physiology and Biochemistry, 2024)

Comparison of muscle structure and transcriptome analysis reveals the mechanism of growth variation in Yangtze sturgeon (Acipenser dabryanus) - Qingzhi Li; Jun Wang; Yeyu Chen; Xiaoyun Wu; Ya Liu; Jiansheng Lai; Mingjiang Song; Feiyang Li; Pengcheng Li; Bin He; Bin Wang; Tao Yan; et al. (Aquaculture, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Multiomics analyses of two Leonurus species illuminate leonurine biosynthesis and its evolution - Peng Li; Meng-Xiao Yan; Pan Liu; Dan-Jie Yang; Ze-Kun He; Yun Gao; Yan Jiang; Yu Kong; Xin Zhong; Sheng Wu; Jun Yang; Hong-Xia Wang; et al. (Molecular Plant, 2024)

Instability in a carbon pool driven by multiple dissolved organic matter sources in a eutrophic lake basin: Potential factors for increased greenhouse gas emissions - Jie Ma; Muchun Zhou; Yu Peng; Ya Tuo; Chuanqiao Zhou; Kexin Liu; Yilin Huang; Fei He; Qiuying Lai; Zhihui Zhang; Tsuyoshi Kinouchi; Shuyin Li; et al. (Journal of Environmental Management, 2024)

Unlocking the potential of N-acetylcysteine: Improving hepatopancreas inflammation, antioxidant capacity and health in common carp (Cyprinus carpio) via the MAPK/NF-κB/Nrf2 signalling pathway - Rui Zhu; Guo-Jun Shang; Bao-Yuan Zhang; Hao-Tong Wang; Liang Li; Xiao-fang Wei; Deng-Lai Li; Zhi-Yong Yang; Zi-Hui Qu; Ya-Nan Quan; Si-Ying Liu; Yin-Tao Wang; et al. (Fish & Shellfish Immunology, 2024)

Simultaneously tuning oxygen reduction pathway and charge transfer dynamics toward sacrificial agent-free photocatalytic H2O2 production for in-situ water disinfection - Ya-Ya Yang; Hai Guo; Da-Wei Huang; Lu Li; Hui-Yun Liu; Long Sui; Qian Wu; Jing-Jing Zhu; Lei Zhang; Cheng-Gang Niu (Chemical Engineering Journal, 2024)

A metal-phenolic network-assembled nanotrigger evokes lethal ferroptosis via self-supply loop-based cytotoxic reactions - Xinping Zhang; Yuxin Guo; Xiaoyang Liu; Shun-Yu Wu; Ya-Xuan Zhu; Shao-Zhe Wang; Qiu-Yi Duan; Ke-Fei Xu; Zi-Heng Li; Xiao-Yu Zhu; Guang-Yu Pan; Fu-Gen Wu (Chemical Engineering Journal, 2024)

Advances in regulating vitamin K2 production through metabolic engineering strategies - Yan Liu; Jian Wang; Jun-bao Huang; Xiang-fei Li; Yu Chen; Kun Liu; Ming Zhao; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Wei Tao; Jing Wu; et al. (World Journal of Microbiology and Biotechnology, 2024)

Isolation and characterization of 55 SNP markers in Triplophysa (Hedinichthys) yarkandensis macroptera - Qiang Li; Yeyu Chen; Hongyu Ke; Zhongmeng Zhao; Han Zhao; Jiansheng Lai; Xiaoyun Wu; Mingjiang Song; Feiyang Li; Ya Liu (Conservation Genetics Resources, 2023)

Fluid mud induced by periodic tidal advection and fine-grained sediment settling in the Yangtze estuary - Hao Wu; Jieping Tang; Weihua Li; Fei Xing; Haifei Yang; Fan Zhang; Ya Ping Wang (Frontiers in Marine Science, 2023)
This study presents in-situ observations of fluid mud in the Yangtze Estuary via a bottom tripod. Six occurrences of periodic fluid muds (F1-F6) were observed at high slack water, with suspended sediment concentration (SSC) exceeding 10 kg/m 3 . The thickness of the fluid mud varied across the six occurrences, reaching a maximum of 0.32m. Notably, temperature and salinity anomalies were observed within the fluid mud. The formation of fluid mud was found to be influenced by turbulence, with turbulence kinetic energy (TKE) below 5×10 -4 m 2 /s 2 favoring settling as the primary cause of formation. The critical shear stress ( τ cw ) for fluid mud formation was estimated to be approximately 0.09 Pa. The formation of fluid muds during early tidal cycles was attributed to liquefaction and bed erosion resulting from strong waves. However, in most cases, the wave energy was insufficient for erosion, suggesting that advection played a role in sediment supply during the subsequent tide cycles. The increased cross-channel current velocity during flood facilitated the lateral transport of a significant amount of eroded sediment from shallow water into the channel. Due to its short duration, the fluid mud layer was entrained by the current before consolidation. Enhanced turbulence led to the breakdown of fluid mud at the early ebb. The critical τ cw for fluid mud breakdown depended on the density and duration of the fluid mud, with a maximum value of up to 0.70 Pa. The absence of the fluid mud layer during low slack water and neap tide was associated with a reduction in advection and tidal pumping, disrupting the original sediment balance between supply and demand. These data provide valuable insights into the formation and breakdown of fluid mud, contributing to estuarine hydrodynamic modeling studies and enhancing the understanding of estuary dynamics.

Dynamic human exposure to airborne bacteria-associated antibiotic resistomes revealed by longitudinal personal monitoring data - Rong-min Zhang; Xin-lei Lian; Li-wei Shi; Liuyiqi Jiang; Shan-shan Chen; Wen-qing Haung; Jia-en Wu; Fei-jing Wu; Jian Sun; Xiao-ping Liao; Yun-xiao Chong; Ya-hong Liu; et al. (Science of The Total Environment, 2023)

Single-cell RNA sequencing reveals a hierarchical transcriptional regulatory network of terpenoid biosynthesis in cotton secretory glandular cells - Jia-Ling Lin; Longxian Chen; Wen-Kai Wu; Xiao-Xiang Guo; Cheng-Hui Yu; Min Xu; Gui-Bin Nie; Jun-ling Dun; Yan Li; Baofu Xu; Ling-Jian Wang; Xiao-Ya Chen; et al. (Molecular Plant, 2023)

Effect of melting combined with ice recrystallization on porous starch preparation: Pore-forming properties, granular morphology, functionality, and multi-scale structures - Chen Zhang; Shi-Yi Wang; Chu-Yun Wu; Jing-Jing Li; Ling-Zhi Zhang; Zhi-Juan Wang; Qiao-Quan Liu; Jian-Ya Qian (Food Research International, 2023)

Physiological and biochemical changes in leaf abscission of Cyclocarya paliurus stem segments in vitro - Qiu-Ying Li; Shuang Wang; Gao-Yin Wu; Ya Tan; Ying-Ying Liu; Cong-Jun Yuan; Shuang-Gui Geng; Ying-Liang Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Endophytic Bacillus sp. R1 and Its Roles in Assisting Phytoremediation and Alleviating the Toxicity of Aluminum Combined Phenanthrene Contaminations in Brassica napus - Li-rong Fang; Xue-cheng Yang; Chun-ya Wu; Kai Sun; Mallavarapu Megharaj; Wei He (Current Microbiology, 2023)

Salidroside Ameliorates Ischemia/Reperfusion-Induced Human Cardiomyocyte Injury by Inhibiting the Circ_0097682/miR-671-5p/USP46 Pathway - Yuyang Yang; Fangqian Liang; Jingyuan Gao; Jian Li; Chunhua Jiang; Wei Xie; Shujuan Wu; Ya Wang; Jing Yi (Cardiovascular Toxicology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Socioeconomic status, lifestyle and risk of incident dementia: a prospective cohort study of 276730 participants - Ya-Nan Ou; Yan-Bo Zhang; Yu-Zhu Li; Shu-Yi Huang; Wei Zhang; Yue-Ting Deng; Bang-Sheng Wu; Lan Tan; Qiang Dong; An Pan; Ren-Jie Chen; Jian-Feng Feng; et al. (GeroScience, 2023)

TBtools-II: A “one for all, all for one” bioinformatics platform for biological big-data mining - Chengjie Chen; Ya Wu; Jiawei Li; Xiao Wang; Zaohai Zeng; Jing Xu; Yuanlong Liu; Junting Feng; Hao Chen; Yehua He; Rui Xia (Molecular Plant, 2023)

Dietary cultured supernatant mixture of Cetobacterium somerae and Lactococcus lactis improved liver and gut health, and gut microbiota homeostasis of zebrafish fed with high-fat diet - Shenghui Li; Hongwei Yang; Ya Jin; Qiang Hao; Shubin Liu; Qianwen Ding; Yuanyuan Yao; Yalin Yang; Chao Ran; Chenglong Wu; Shengkang Li; Kaimin Cheng; et al. (Fish & Shellfish Immunology, 2023)

Integrated metabolomic and transcriptomic responses to heat stress in a high-altitude fish, Triplophysa siluroides - Yeyu Chen; Xiaoyun Wu; Pengcheng Li; Ya Liu; Mingjiang Song; Feiyang Li; Jun Ou; Jiansheng Lai (Fish & Shellfish Immunology, 2023)

Dose-response formation of N7-(3-benzo[1,3]dioxol-5-yl-2-hydroxypropyl)guanine in liver and urine correlates with micronucleated reticulocyte frequencies in mice administered safrole oxide - Kuen-Yuh Wu; Yu-Tzu Wei; Yu-Syuan Luo; Li-Chin Shen; Bao-Suei Chang; Ya-Yin Chen; Yan-Chi Huang; Hui-Fen Huang; Wen-Sheng Chung; Su-Yin Chiang (Food and Chemical Toxicology, 2023)

Performance degradation by column foot damage: From column foot joints to frames - Ya-Jie Wu; Chen Liu; Qi-Fang Xie; Li-Peng Zhang; Tian-Wei Zhang; Jia-Jia Ou (Engineering Structures, 2023)

Bioinspired yeast-based β-glucan system for oral drug delivery - Ya Wu; Pengyun Li; Zongzhe Jiang; Xiaolei Sun; Huqiang He; Pijun Yan; Yong Xu; Yong Liu (Carbohydrate Polymers, 2023)

Isolation and characterization of 73 SNP markers in Schizopygopsis chengi baoxingensis - Mingjiang Song; Yeyu Chen; Xiaoyun Wu; Ya Liu; Feiyang Li; Quan Gong; Jun Ou; Pengcheng Li; Qiaolin Zou; Jiansheng Lai (Conservation Genetics Resources, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Prospects and perspectives on advanced materials for sodium-ion batteries - Zhen-Yi Gu; Xiao-Tong Wang; Yong-Li Heng; Kai-Yang Zhang; Hao-Jie Liang; Jia-Lin Yang; Edison Huixiang Ang; Peng-Fei Wang; Ya You; Fei Du; Xing-Long Wu (Science Bulletin, 2023)

Signaling between sporophytic integuments and developing female gametophyte during ovule development - Zheng Qin; Ya-Nan Wu; Sha Li; Yan Zhang (Plant Science, 2023)

Oxygen Vacancies of Mn/CeOx-H induced non-radical activation of peroxymonosulfate through electron mediation for bisphenol A degradation - Junyong He; Ya Yang; Peidong Hong; Yulian Li; Chao Xie; Zijian Wu; Minqiang Li; Lingtao Kong (Journal of Environmental Chemical Engineering, 2023)

Self-assembly and interaction mechanisms of edible dock protein and flavonoids regulated by the phenolic hydroxyl position - Qian Zhou; Xiao-Jie Wang; Jing Li; Yu-Ru Wu; Wei Wang; Zhen-Yu Yu; Ya-Qing Xiao; Ying-Nan Liu; Shi-Yi Li; Ming-Ming Zheng; Yi-Bin Zhou; Kang Liu (Food Chemistry, 2023)

Flexural properties of ultra-high performance fiber reinforced concrete based on three-dimensional random distribution of steel fibers - Ya Lu; Jingcheng Han; Puyan Wang; Xiangguo Wu; Hyeon-Jong Hwang; Jian Zhou; Ran Li; Sung-Hyun Kim; Ho-Jun Lee (Engineering Structures, 2023)

Advanced electrooxidation of florfenicol using 3D printed Nb2O5/Ti electrodes: Degradation efficiency, dehalogenation performance, and toxicity reduction - Yun-fei Zhang; Jia-le Gao; Shen-gui Chen; Lei Li; Jian-hui Xu; Dan Li; Yu-feng Liu; Xin Quan; Xin Fu; Ya-zi Xie; Jing-nan Wu; Dan-ying Lin; et al. (Chemical Engineering Journal, 2023)

Synergization of an endoplasmic reticulum-targeted iridium(III) photosensitizer with PD-L1 inhibitor for oral squamous cell carcinoma immunotherapy - Jia-Ying Zhou; Qing-Hua Shen; Xiao-Jing Hong; Wu-Ya Zhang; Qiao Su; Wu-Guo Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2023)

Insights into the pyrolysis mechanisms of epoxy resin polymers based on the combination of experiments and ReaxFF-MD simulation - Ming-xin Xu; Jin-yi Di; Ya-chang Wu; Xiang-xi Meng; Haiwen-Ji; Hao Jiang; Ji-hong Li; Qiang Lu (Chemical Engineering Journal, 2023)

A topical thermosensitive hydrogel system with cyclosporine A PEG-PCL micelles alleviates ulcerative colitis induced by TNBS in mice - Chuyao Xiao; Genyun Li; Xiaoyue Li; Dan Wang; Ya Wu; Minghui Sun; Jiangeng Huang; Luqin Si (Drug Delivery and Translational Research, 2023)

Isolation and identification of Eurasian avian-like H1N1 swine influenza virus and evaluation of their pathogenicity and immune protective effects in pigs - Ying Yang; Yunfu Huang; Kun Huang; Yufei Zhang; Xiaotong Hu; Weihua Zou; Chao Wu; Xianfeng Hui; Chengfei Li; Ya Zhao; Xiaomei Sun; Zhong Zou; et al. (Veterinary Microbiology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Undescribed steroidal alkaloids from the bulbs of Fritillaria sinica - Jia-yuan Li; Shi-fei Wu; Ya-ling An; Chang-liang Yao; Shuai Yao; Yong Huang; Wen-long Wei; Jian-qing Zhang; Qi-rui Bi; Hua Qu; De-an Guo (Phytochemistry, 2023)

Mechanisms of feeding cessation in Helicoverpa armigera larvae exposed to Bacillus thuringiensis Cry1Ac toxin - Kaixia Li; Shan Yu; Yihua Yang; Ya-Zhou He; Yidong Wu (Pesticide Biochemistry and Physiology, 2023)

Allelopathy of p-coumaric acid on Limnothrix sp., a bloom-forming cyanobacteria - Liping Wu; Lingzhi Li; Pan Dong; Liang Zhang; Hui Tang; Ya Han; Gengxin Xie (Algal Research, 2023)

Blood-based biomarkers for Alzheimer’s disease: a multicenter-based cross-sectional and longitudinal study in China - Feng Gao; Linbin Dai; Qiong Wang; Chang Liu; Kexue Deng; Zhaozhao Cheng; Xinyi Lv; Yan Wu; Ziyi Zhang; Qingqing Tao; Jing Yuan; Shiping Li; et al. (Science Bulletin, 2023)

Lateral performance of mortise-tenon jointed frames in multi-story traditional heavy timber structures: Mechanism and quantification - Ya-Jie Wu; He-Shou Lin; Lei Wang; Qi-Fang Xie; Li-Peng Zhang (Engineering Structures, 2023)

Preparation of carbon foam from depolymerization-reforming lignin for capacitive deionization - Chun-Ping Li; Ya-Qi Wu; Jia-Jia An; Li-Xin Gao; Da-Quan Zhang; Jin Li; Zhong-Xun An (Desalination, 2023)

Enhanced vitamin K2 production by engineered Bacillus subtilis during leakage fermentation - Meng-jie Zhou; Jing Wu; Liu-xiu Hu; Wen-song Hu; Jun-bao Huang; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Zheng-lian Xue; Yan Liu (World Journal of Microbiology and Biotechnology, 2023)

A systematic review: on the mercaptoacid metabolites of acrylamide, N-acetyl-S-(2-carbamoylethyl)-L-cysteine - Fang-Fang Zhao; Xiao-Li Wang; Ya-Ting Lei; Hong-Qiu Li; Zhi-Ming Li; Xiao-Xiao Hao; Wei-Wei Ma; Yong-Hui Wu; Sheng-Yuan Wang (Environmental Science and Pollution Research, 2023)

A new butenolide with antifungal activity from solid co-cultivation of Irpex lacteus and Nigrospora oryzae - Ya-Mei Wu; Xue-Qiong Yang; Jing-Xin Chen; Ting Wang; Tai-Ran Li; Fan-Rong Liao; Run-Tong Liu; Ya-Bin Yang; Zhong-Tao Ding (Natural Product Research, 2023)

Hexavalent chromate bioreduction by a magnetotactic bacterium Magnetospirillum gryphiswaldense MSR-1 and the effect of magnetosome synthesis. - Siang Chen Wu; Wei-Che Hsiao; Ya-Chun Zhao; Li-Fen Wu (Chemosphere, 2023)

Indoxyl sulfate in atherosclerosis - Cong Lu; Li Wu; Mu-Yao Tang; Yi-Fan Liu; Lei Liu; Xi-Ya Liu; Chun Zhang; Liang Huang (Toxicology Letters, 2023)

Identification and characterization of goat milk key flavor compounds and their precursors in electron beam irradiation and pasteurization on raw - Chunlu Wen; Ya Chen; Madina; Linlu Zhang; Yue Peng; Bai Rong; Linjie Xi; Shengqi Jiang; Jiangtao Yu; Junqing Bai; Niu Wei; Li Kui; et al. (Innovative Food Science & Emerging Technologies, 2023)

Aroma correlation assisted volatilome coupled network analysis strategy to unveil main aroma-active volatiles of Rosa roxburghii - Ya-Hui Ge; Xue Li; Mingzheng Huang; Zhengxu Huang; Manman Wu; Baoqing Sun; Lishuang Wang; Jian-Lin Wu; Na Li (Food Research International, 2023)

The bound polyphenols of foxtail millet (Setaria italica) inner shell inhibit breast cancer by promoting lipid accumulation-induced autophagic death - Li-chao Zhang; Ya-ning Liu; Xiao-qin La; Shuai-tao Li; Li-na Wen; Ting Liu; Han-qing Li; Ai-ping Li; Haitao Wu; Chang-xin Wu; Zhuo-yu Li (Food and Chemical Toxicology, 2023)

Effects of microplastics in aquatic environments on inflammatory bowel disease - Jiali Ji; Xinyue Wu; Xi Li; Ya Zhu (Environmental Research, 2023)

Combined effects of light pollution and vegetation height on behavior and body weight in a nocturnal rodent - Ling-Ying Shuai; Li-Qing Wang; Yang Xia; Jin-Yu Xia; Kang Hong; Ya-Nan Wu; Xin-Yi Tian; Fu-Shun Zhang (Environmental Pollution, 2023)

New insights into the phylogeny and evolution of Chinese Ovophis (Serpentes, Viperidae): Inferred from multilocus data - Yang‐Mei Zeng; Ke Li; Qin Liu; Ya‐Yong Wu; Shao‐Bing Hou; Gui‐Gang Zhao; Sang Ngoc Nguyen; Peng Guo; Lei Shi (Zoologica Scripta, 2023)
The Asian pitviper genus Ovophis is a group of venomous snakes widely distributed in mid to high elevation mountains in Asia, and presently five species are recognised. However, its systematics, species diversity and species distribution boundaries remain poorly understood. We reconstructed the phylogenetic relationships and explored species diversity of Chinese Ovophis based on two mitochondrial fragments (Cyt b and ND4) and four nuclear genes ( BACH1 , c‐mos , Rag1 , NT3 ) and also conducted a morphological comparison between focal species. Our results indicated that the species diversity had been underestimated within Ovophis and we described a population from southern Yunnan, China, as a new taxon, naming it as Ovophis malhotrae sp . nov . Based on more extensive sampling, we redefined the distribution of O. monticola and O. makazayazaya in China. Divergence date estimation suggested that Ovophis originated at about 16.79 Ma in the middle Miocene.

Dietary zearalenone alters gill epithelial morphology and subsequent risk of infection: Insights from a freshwater grass carp (Ctenopharyngodon idella) model - Hong-Yun Zhang; Ya-Li Wang; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Hai-Feng Mi; Sheng-Yao Kuang; Ling Tang; Shu-wei Li; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Formation and transport of fluid mud triggered by typhoon events in front of the subaqueous Changjiang Delta - Jieping Tang; Hao Wu; Fei Xing; Fan Zhang; Bixuan Tang; Gaocong Li; Ya Ping Wang (Marine Geology, 2023)

Non-thermal effects of microwave irradiation alleviates postharvest chilling injury of peach fruit by retarding phenolic accumulation and enhancing membrane stability - Ke Wang; Ge Zhu; Ya-li Li; Shu-qi Chen; Arif Rashid; Xiao-tong Wang; Xin-yu Wu (Food Chemistry, 2023)

What affects the accuracy and applicability of determining wastewater sludge water content via low-field nuclear magnetic resonance? - Ya-Li Zhang; Ping Sun; Bing-Bing Dai; Shao-Ming Zheng; Dan-Di Ran; Tian-Xin Wu; Raymond Jianxiong Zeng; Hou-Feng Wang (Environmental Research, 2023)

Pulsed counterclockwise rotation of the southwestern Sichuan Basin in response to the India-Asia convergence during 128-42 Ma - Qi Shen; Chun-Sheng Jin; Wen-Tian Liang; Chuan-Zhi Li; Hui-Hui Yang; Ya-Zhou Ran; Xuan He; Guan-Zuo Wu; Kai Jiang; Jian-Gang Li; Peng Han; Si-Hua Yuan (Earth and Planetary Science Letters, 2023)

A single fluorescent probe reveals changes in endoplasmic reticulum–mitochondria contact in hepatocytes during ferroptosis - Ling-Li Wang; Ya-Ru Zhang; Ming-Hua Zheng; Xuan Wang; Xue Wu; Jing-Yi Jin (Chemical Engineering Journal, 2023)

4-OI ameliorates bleomycin-induced pulmonary fibrosis by activating Nrf2 and suppressing macrophage-mediated epithelial-mesenchymal transition - Ya-xian Wu; Ya-ru Zhang; Feng-juan Jiang; Shuai He; Yan-li Zhang; Dan Chen; Ying Tong; Yun-juan Nie; Qing-feng Pang (Inflammation Research, 2023)

Isolation and characterization of 46 SNP markers in Gymnocypris chilianensis - Ya Liu; Wenqiong Wu; Siyi Zhu; Yeyu Chen; Xiaoyun Wu; Jiansheng Lai; Mingjiang Song; Feiyang Li; Qiang Li (Conservation Genetics Resources, 2023)

Colonic mechanism of serum NAD+ depletion induced by DEHP during pregnancy - Yun Hong; Xia Ning; Yue-yue Liang; Xiao-lu Li; Ya Cui; Wei Wu; Yang Cai; Shuai Zhao; Meng Zhu; Tian-xiao Zhong; Hua Wang; De-xiang Xu; et al. (Science of The Total Environment, 2023)

Turn on fluorescence detection of curcumin in food matrices by the novel fluorescence sensitizer - Ya-Qian Wang; Li Li; Jin Yin; Xu Yu; Xiaowei Wu; Li Xu (Analytica Chimica Acta, 2023)

Triassic igneous activities in the east flank of the East Kunlun orogenic belt: the Daheba complex example - Nan Tian; Feng-Yue Sun; Zhong-Cui Pan; Liang Li; Yan Gu; Dong-Qian Wu; Jia-Fang Deng; Zhe-Dong Liu; Li Wang; Ya-Jing Zhang (International Geology Review, 2023)

In-situ construction of Mn0.2Cd0.8S/NiB composite for highly efficient full spectrum-driven photocatalytic H2 evolution - Ya Li; Ya-Nan Wu; Yi Yang; Yan Xiong; Yi-Ke Li; Qun-Zeng Huang (Journal of Environmental Chemical Engineering, 2023)

Assessment of toxic mechanisms and mode of action to three different levels of species for 14 antibiotics based on interspecies correlation, excess toxicity, and QSAR - Jin J. Li; Ya X. Yue; Jie F. Jiang; Sheng J. Shi; Hui X. Wu; Yuan H. Zhao; Fei F. Che (Chemosphere, 2023)

BSNet: Boundary-semantic-fusion network for farmland parcel mapping in high-resolution satellite images - Wang Shunying; Zhou Ya'nan; Yang Xianzeng; Feng Li; Wu Tianjun; Luo Jiancheng (Computers and Electronics in Agriculture, 2023)

The genomes of medicinal skullcaps reveal the polyphyletic origins of clerodane diterpene biosynthesis in the family Lamiaceae - Haixiu Li; Song Wu; Ruoxi Lin; Yiren Xiao; Ana Luisa Malaco Morotti; Ya Wang; Meytal Galilee; Haowen Qin; Tao Huang; Yong Zhao; Xun Zhou; Jun Yang; et al. (Molecular Plant, 2023)

Exposure levels of PCDD/Fs from co-landfill scenario with MSW and stabilized fly ash during hydrolysis-acidogenesis - Mingxue Xin; Yingjie Sun; Weihua Li; Junquan Yin; Yinkai Wu; Yuyang Long; Rongxing Bian; Ya-nan Wang; Huawei Wang; Yufei Yang; Qifei Huang (Journal of Cleaner Production, 2023)

Boosting the photocatalytic hydrogen evolution and NO removal via synergistic effects of in-situ Pt NPs formation and titanium integration in Zr-Porphyrin MOFs - Ruolan Li; Zongqian Wu; Ya Chen; Xingyan Liu; Weiwei Guo; Yumin Huang; Min Fu; Youzhou He (Fuel, 2023)

Unraveling the antibacterial mechanism of Lactiplantibacillus plantarum MY2 cell-free supernatants against Aeromonas hydrophila ST3 and potential application in raw tuna - Di Wang; Yangfan Liu; Xupeng Li; Shengjun Chen; Jianchao Deng; Chunsheng Li; Chuang Pan; Yueqi Wang; Huan Xiang; Yang Feng; Xianqing Yang; Laihao Li; et al. (Food Control, 2023)

The protective role of vitamin C on intestinal damage induced by high-dose glycinin in juvenile Rhynchocypris lagowskii Dybowski - Rui Zhu; Zongyu Liu; Minghui Lu; Xueqin Wu; Xueyuan Zhao; Hong-He Wang; Ya-Nan Quan; Li-Fang Wu (Fish & Shellfish Immunology, 2023)

Theoretically thermal-varying models of the neutral axis position for local damage detection of bridge girders - Guang-Ming Wu; Sheng-Li Li; Ting-Hua Yi; Xiu-Dao Mei; Ya-Fei Wang (Engineering Structures, 2023)

The real-time detection of acupuncture-induced extracellular ATP mobilization in acupoints and exploration of its role in acupuncture analgesia - Wei-Min Zuo; Yu-Jia Li; Kai-Yu Cui; Dan Shen; Di Zhang; Ya-Wen Zheng; Meng Huang; Yong Wu; Xue-Yong Shen; Li-Na Wang; Guang-Hong Ding (Purinergic Signalling, 2023)

Analysis of PAT1 subfamily members in the GRAS family of upland cotton and functional characterization of GhSCL13-2A in Verticillium dahliae resistance - Chen Chen; Li-Li Lu; Shu-Ya Ma; Yan-Peng Zhao; Na Wu; Wen-Jie Li; Li Ma; Xian-Hui Kong; Zong-Ming Xie; Yu-Xia Hou (Plant Cell Reports, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Response of sediment microbial communities to different levels of PAC contamination and exposure time - Xiao Xiao; Ya-Li Zhang; Zi-An Zhou; Fan Wu; Hou-Feng Wang; Xin Zong (Science of The Total Environment, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Proactive therapeutic drug monitoring of vincristine in pediatric and adult cancer patients: current supporting evidence and future efforts - Chun-Ying Wu; Guan-Ting Li; Chen-Chao Chu; Hong-Li Guo; Wei-Rong Fang; Tao Li; Yong-Ren Wang; Jing Xu; Ya-Hui Hu; Li Zhou; Feng Chen (Archives of Toxicology, 2023)

Personalizing atomoxetine dosing in children with ADHD: what can we learn from current supporting evidence - Di Fu; Hong-Li Guo; Ya-Hui Hu; Wei-Rong Fang; Qian-Qi Liu; Jing Xu; Dan-Dan Wu; Feng Chen (European Journal of Clinical Pharmacology, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Variations in Asian summer monsoon and hydroclimate during Heinrich stadials 4 revealed by stalagmite stable isotopes and trace elements - Yao Wu; Ting-Yong Li; Jun-Yun Li; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Yan Yang; Jing-Yao Zhao; Chao-Jun Chen; Ming-Qiang Liang; Si-Ya Xiao; Hai-Ying Qiu; et al. (Quaternary Science Reviews, 2023)

Insights into the influence on 2,4,6-trichlorophenol microbial reductive dechlorination process by exposure to microplastics - Jia-Qi Yang; Zhi-Ling Li; Bin Wu; Ya-Ru Jin; Di Cao; Jun Nan; Xue-Qi Chen; Wen-Zong Liu; Shu-Hong Gao; Ai-Jie Wang (Journal of Hazardous Materials, 2023)

Biochemical, transcriptomic and metabolomic responses to total dissolved gas supersaturation and their underlying molecular mechanisms in Yangtze sturgeon (Acipenser dabryanus) - Yeyu Chen; Xiaoyun Wu; Xiaoqing Liu; Jiansheng Lai; Ya Liu; Mingjiang Song; Feiyang Li; Quan Gong (Environmental Research, 2023)

Synergistic effect of ferrous ion-activated hydrogen peroxide and persulfate on the degradation of phthalates in aquatic environments by non-target analysis - Ya Wu; Rongmiao Fang; Hao Li; Jingyao Li; Dan Zhao; NaNa Chang; Huaming Sun; Jun Shi (Chemical Engineering Journal, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

Expanding the valorization of waste mushroom substrates in agricultural production: progress and challenges - Ya Gao; Zhibin Wu; Weiming Li; Haibo Sun; Youzheng Chai; Tianyou Li; Chao Liu; Xiaomin Gong; Yunshan Liang; Pufeng Qin (Environmental Science and Pollution Research, 2023)

Liming shifts the chemical properties and microbial community structures of peanut soils with different initial pH values - Ya Lu; Hongcui Dai; Kazem Zamanian; Qiqi Sun; Caibin Wang; Zhengfeng Wu; Yongmei Zheng; Lin Li; Shubo Wan; Tianyi Yu (Applied Soil Ecology, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

STING/NF-κB/IL-6-Mediated Inflammation in Microglia Contributes to Spared Nerve Injury (SNI)-Induced Pain Initiation - Jia Sun; Ya-qun Zhou; Bing-yang Xu; Jia-yan Li; Long-qing Zhang; Dan-yang Li; Shuang Zhang; Jia-yi Wu; Shao-jie Gao; Da-wei Ye; Wei Mei (Journal of Neuroimmune Pharmacology, 2022)

Low-Level Environmental Per- and Polyfluoroalkyl Substances and Preterm Birth: A Nested Case–Control Study Among a Uyghur Population in Northwestern China - Bo-Yi Yang; Jianhua Wu; Xilong Niu; Chuanjiang He; Michael S. Bloom; Maihefuzaimu Abudoukade; Mairiyemu Abulizi; Aimin Xu; Beibei Li; Li Li; Xuemei Zhong; Qi-Zhen Wu; et al. (Exposure and Health, 2022)

Genome-Wide Identification, Expression, and Interaction Analysis of BEL-Like Homeodomain Gene Family in Peach - Hui-feng Li; Ya-ting Wu; Qiang Zhao; Qing-long Dong (Biochemical Genetics, 2022)

U–Pb geochronology and Hf isotope characterization of detrital zircons from Nanhua System of northeastern Guangxi and their constraints on the southwestern suture zone between Yangtze and Cathaysia blocks, South China - Xiaofang Gou; Ya Qin; Zuohai Feng; Huanzhang Li; Yonggao Huang; Jie Wu; Yu Cui; Longfei Ma; Chunzeng Wang (Arabian Journal of Geosciences, 2022)

Flowering characteristics and mating system of Fritillaria cirrhosa (Liliaceae), an endangered plant in China - Yanzhu Ma; Zhijia Cui; Chun Ya Cheng; Ran Li; Haixu Wu; Ling Jin; Yi Ma; Zhenheng Wang (Brazilian Journal of Botany, 2022)

New polymerized sesquiterpene lactones from Ainsliaea yunnanensis and their activity evaluation - Na Zhou; Jin-Jie Li; Yong Wu; Ze-Yu Wang; Xin Wang; Zhi-Peng Yin; Xin-Peng Wang; Yi-Ran Liu; Xiao-Ya Shang (Natural Product Research, 2022)

Siccirubricoccus soli sp. nov., a novel bacterial species isolated from Jiaozi Mountain soil - Guo-Xing Zhu; Ya-Jie Wu; Yan-Ru Cao; Bing-Jun Fan; Yu Jiao; Xiu-Li Hou; Zi-Chao Liu; Yue Zhang; Jiang-Bo He; Lian-Ming Liang (Antonie van Leeuwenhoek, 2022)

Development of 45 SNP markers in Triplophysa hsutschouensis based on RAD sequencing - Ya Liu; Jiansheng Lai; Zhongmeng Zhao; Hongyu Ke; Han Zhao; Yeyu Chen; Xiaoyun Wu; Qiang Li (Conservation Genetics Resources, 2022)

Elder people can be more susceptible to the association between short-term ambient air pollution and sleep disorder outpatient visits: a time-series study - Yu-Meng Zhou; Shu-Jie An; Yi Cao; Chen Xu; Xiao-Ling Liu; Chun-Yan Yao; Xiang Li; Na Wu; Cheng-Ying Li; Long Wu; Ya-Fei Li; Ai-Ling Ji; et al. (Environmental Science and Pollution Research, 2022)

Inhibition of visfatin alleviates sepsis-induced intestinal damage by inhibiting Hippo signaling pathway - Zhong-Shen Kuang; Yu-Xin Leng; Ning Yang; Zheng-Qian Li; Ya-Nan Zong; Deng-Yang Han; Yue Li; Jin-Dan He; Xing-Ning Mi; Zhu-Kai Cong; Xi Zhu; Chang-Yi Wu; et al. (Inflammation Research, 2022)
Background The aim of this study is to investigate role of Visfatin, one of the pro-inflammatory adipokines, in sepsis-induced intestinal injury and to clarify the potential mechanism. Methods C57BL/6 mice underwent cecal ligation and puncture (CLP) surgery to establish sepsis model in vivo. Intestinal epithelial cells were stimulated with LPS to mimic sepsis-induced intestinal injury in vitro. FK866 (the inhibitor of Visfatin) with or without XMU-MP-1 (the inhibitor of Hippo signaling) was applied for treatment. The expression levels of Visfatin, NF-κB and Hippo signaling pathways-related proteins were detected by western blot or immunohistochemistry. The intestinal cell apoptosis and intestinal injury were investigated by TUNEL staining and H&E staining, respectively. ELISA was used to determine the production of inflammatory cytokines. Results The expression of Visfatin increased in CLP mice. FK866 reduced intestinal pathological injury, inflammatory cytokines production, and intestinal cell apoptosis in sepsis mice. Meanwhile, FK866 affected NF-κB and Hippo signaling pathways. Additionally, the effects of FK866 on inflammatory response, apoptosis, Hippo signaling and NF-κB signaling were partly abolished by XMU-MP-1, the inhibitor of Hippo signaling. In vitro experiments also revealed that FK866 exhibited a protective role against LPS-induced inflammatory response and apoptosis in intestinal cells, as well as regulating NF-κB and Hippo signaling, whereas addition of XMU-MP-1 weakened the protective effects of FK866. Conclusion In short, this study demonstrated that inhibition of Visfatin might alleviate sepsis-induced intestinal injury through Hippo signaling pathway, supporting a further research on Visfatin as a therapeutic target.

Prediction of Water Inflow into Tunnel Crossing Intersecting Faults Based on IDB Seepage Model - Jing Wu; Li Wu; Ya-ni Lu; Yan-hua Han; Jun-jie Jiang (Geotechnical and Geological Engineering, 2022)

Exposure characteristics of phthalate metabolites among the Zunyi cohort of pregnant women in Southwest China - Juan Liao; Derong Fang; Yijun Liu; Shimin Xiong; Xia Wang; Yingkuan Tian; Haonan Zhang; Songlin An; Caidie He; Wei Chen; Xiang Liu; Nian Wu; et al. (Environmental Science and Pollution Research, 2022)

PLXDC2 enhances invadopodium formation to promote invasion and metastasis of gastric cancer cells via interacting with PTP1B - Bin Wu; Yan-xia Wang; Jun-jie Wang; Dong-fang Xiang; Meng-si Zhang; Ze-xuan Yan; Wen-ying Wang; Jing-ya Miao; Xi Lan; Jia-jia Liu; Zheng-yan Li; Chuan Li; et al. (Clinical & Experimental Metastasis, 2022)
Plexin-domain containing 2 (PLXDC2) has been reported as an oncoprotein in several human malignancies. However, its expression and roles in gastric cancer remain largely unclear. In this study, we found that PLXDC2 was highly expressed in gastric cancer tissues, and the expression levels were positively correlated with clinicopathological features, but negatively with the patients’ outcome. Cox regression analysis identified PLXDC2 as an independent prognostic indicator for the patients. Knockdown of PLXDC2 markedly suppressed the in vitro invasion and in vivo metastasis of gastric cancer cells, while overexpression of PLXDC2 resulted in opposite effects. Mechanistically, PLXDC2 enhanced the level of phosphorylated Cortactin (p-Cortactin) by physically interacting with protein tyrosine phosphatase 1B (PTP1B), an important dephosphorylase, to prevent its dephosphorylating of p-Cortactin, thereby promoting the formation of invadopodia. Collectively, our results indicate that PLXDC2 contributes to the invasion and metastasis of gastric cancer by inhibiting PTP1B to facilitate the invadopodium formation, and may serve as a potential prognostic biomarker and a therapeutic target for this disease.

Testing the isotopic equilibrium fractionation on active speleothem based on cave monitoring - Yang-Yang Huang; Ting-Yong Li; Chao-Jun Chen; Ran Huang; Tao Wang; Yao Wu; Si-Ya Xiao; Yu-Zhen Xu; Hai-Ying Qiu; Yan Yang; Jun-Yun Li (Journal of Earth System Science, 2022)

Isolation and characterization of 45 SNP markers in Triplophysa tenuis - Ya Liu; Yeyu Chen; Jiansheng Lai; Hongyu Ke; Zhongmeng Zhao; Han Zhao; Xiaoyun Wu; Jian Zhou; Qiang Li (Conservation Genetics Resources, 2022)

The Impact of Urban Expansion on Plant Diversity Change in Karst Regions of Southwest China - Shengtian Yang; Chaojun Li; Hezhen Lou; Ya Luo; Pengfei Wang; Jun Zhang; Xi Li; Xijin Wu (Chinese Geographical Science, 2022)

Recent advances in the structure, synthesis, and applications of natural polymeric hydrogels - Khalid Gul; Ren-You Gan; Cui-Xia Sun; Ge Jiao; Ding-Tao Wu; Hua-Bin Li; Ahmad Kenaan; Harold Corke; Ya-Peng Fang (Critical Reviews in Food Science and Nutrition, 2022)

Isolation and characterization of 112 SNP markers in Yellowfin seabream (Acanthopagrus latus) using RAD sequencing - Ke-Cheng Zhu; Ya-Ling Li; Wei-Bin Wu; Bao-Suo Liu; Hua-Yang Guo; Nan Zhang; Liang Guo; Dian-Chang Zhang (Conservation Genetics Resources, 2022)

Discovery of Nanos1 and Nanos2/3 as Germ Cell Markers During Scallop Gonadal Development - Liangjie Liu; Tian Liu; Shaoxuan Wu; Yajuan Li; Huilan Wei; Lijing Zhang; Ya Shu; Yaxin Yang; Qiang Xing; Shi Wang; Lingling Zhang (Marine Biotechnology, 2022)

Molecular characterization of two MAPK genes and their thermotolerant functions in a high temperature acclimated strain of Neoseiulus barkeri - Ya-Ying Li; Chuan-Bei Tian; Yi-Xia Wu; Tian-Di Niu; Wen-Qiang Chu; Huai Liu (BioControl, 2022)

Functional traits explain the consistent resistance of biodiversity to plant invasion under nitrogen enrichment - Shao‐peng Li; Pu Jia; Shu‐ya Fan; Yingtong Wu; Xiang Liu; Yani Meng; Yue Li; Wen‐sheng Shu; Jin‐tian Li; Lin Jiang (Ecology Letters, 2022)
Elton's biotic resistance hypothesis, which posits that diverse communities should be more resistant to biological invasions, has received considerable experimental support. However, it remains unclear whether such a negative diversity–invasibility relationship would persist under anthropogenic environmental change. By using the common ragweed ( Ambrosia artemisiifolia ) as a model invader, our 4‐year grassland experiment demonstrated consistently negative relationships between resident species diversity and community invasibility, irrespective of nitrogen addition, a result further supported by a meta‐analysis. Importantly, our experiment showed that plant diversity consistently resisted invasion simultaneously through increased resident biomass, increased trait dissimilarity among residents, and increased community‐weighted means of resource‐conservative traits that strongly resist invasion, pointing to the importance of both trait complementarity and sampling effects for invasion resistance even under resource enrichment. Our study provides unique evidence that considering species’ functional traits can help further our understanding of biotic resistance to biological invasions in a changing environment.

The importance of compound-specific radiocarbon analysis in source identification of polycyclic aromatic hydrocarbons: A critical review - Miaolei Ya; Yuling Wu; Xinhong Wang; Yongyu Li; Guanyong Su (Critical Reviews in Environmental Science and Technology, 2022)

Analysis and Research on Blasting Network Delay of Deep-Buried Diversion Tunnel Crossing Fault Zone Based on EP-CEEMDAN-INHT - Jing Wu; Li Wu; Miao Sun; Ya-ni Lu; Yan-hua Han (Geotechnical and Geological Engineering, 2022)

Numerical simulation of water inrush in a tunnel crossing faults: impacts of fault width, damage zone width, and fault permeability - Jing Wu; Xintong Wang; Li Wu; Ya-ni Lu; Yan-hua Han (Arabian Journal of Geosciences, 2022)

Single-cell RNA sequencing reveals Nestin+ active neural stem cells outside the central canal after spinal cord injury - Muya Shu; Xiaoyu Xue; Hu Nie; Xianming Wu; Minghan Sun; Lianyong Qiao; Xing Li; Bai Xu; Zhifeng Xiao; Yannan Zhao; Yongheng Fan; Bing Chen; et al. (Science China Life Sciences, 2022)

Overexpression of the PLK4 Gene as a Novel Strategy for the Treatment of Autosomal Recessive Microcephaly by Improving Centrosomal Dysfunction - Ya-Song Xu; Zhi-Ying Su; Li Sun; Xiao-Mei Yang; Shi-Yu Sun; Xiao-Fei Ji; Yi-Zhen Ji; Su-Qing Zhang; Jie Tian; Qi-Chang Wu (Journal of Molecular Neuroscience, 2021)

External evaluation of published population pharmacokinetic models of polymyxin B - Ya-qian Li; Kai-feng Chen; Jun-jie Ding; Hong-yi Tan; Nan Yang; Ya-qi Lin; Cui-fang Wu; Yue-liang Xie; Guo-ping Yang; Jing-Jing Liu; Qi Pei (European Journal of Clinical Pharmacology, 2021)

Discovery of Plasma Membrane-Associated RNAs through APEX-seq - Erzhong Wu; Xuzhen Guo; Xueyi Teng; Ruijin Zhang; Fahui Li; Ya Cui; Dongdong Zhang; Qinghua Liu; Jianjun Luo; Jiangyun Wang; Runsheng Chen (Cell Biochemistry and Biophysics, 2021)

Enhanced expression of DNA methyltransferase 1-associated protein1 gene thermotolerance in a high-temperature acclimated predatory mite Neoseiulus barkeri - Ya-Ying Li; Chuan-Bei Tian; Yi-Xia Wu; Tian-Di Niu; Hao Wang; Wen-Hui Fan; Huai Liu (BioControl, 2021)

Novel Alcaligenes ammonioxydans sp. nov. from wastewater treatment sludge oxidizes ammonia to N 2 with a previously unknown pathway - Meng‐Ru Wu; Ting‐Ting Hou; Ying Liu; Li‐Li Miao; Guo‐Min Ai; Lan Ma; Hai‐Zhen Zhu; Ya‐Xin Zhu; Xi‐Yan Gao; Craig W. Herbold; Michael Wagner; De‐Feng Li; et al. (Environmental Microbiology, 2021)
Summary Heterotrophic nitrifiers are able to oxidize and remove ammonia from nitrogen‐rich wastewaters but the genetic elements of heterotrophic ammonia oxidation are poorly understood. Here, we isolated and identified a novel heterotrophic nitrifier, Alcaligenes ammonioxydans sp. nov. strain HO‐1, oxidizing ammonia to hydroxylamine and ending in the production of N 2 gas. Genome analysis revealed that strain HO‐1 encoded a complete denitrification pathway but lacks any genes coding for homologous to known ammonia monooxygenases or hydroxylamine oxidoreductases. Our results demonstrated strain HO‐1 denitrified nitrite (not nitrate) to N 2 and N 2 O at anaerobic and aerobic conditions respectively. Further experiments demonstrated that inhibition of aerobic denitrification did not stop ammonia oxidation and N 2 production. A gene cluster ( dnfT1RT2ABCD ) was cloned from strain HO‐1 and enabled E . coli accumulated hydroxylamine. Sub‐cloning showed that genetic cluster dnfAB or dnfABC already enabled E . coli cells to produce hydroxylamine and further to 15 N 2 from ( 15 NH 4 ) 2 SO 4 . Transcriptome analysis revealed these three genes dnfA , dnfB and dnfC were significantly upregulated in response to ammonia stimulation. Taken together, we concluded that strain HO‐1 has a novel dnf genetic cluster for ammonia oxidation and this dnf genetic cluster encoded a previously unknown pathway of di rect amm onia ox idation (Dirammox) to N 2 .

On the origin of SARS-CoV-2—The blind watchmaker argument - Chung-I Wu; Haijun Wen; Jian Lu; Xiao-dong Su; Alice C. Hughes; Weiwei Zhai; Chen Chen; Hua Chen; Mingkun Li; Shuhui Song; Zhaohui Qian; Qihui Wang; et al. (Science China Life Sciences, 2021)

Prediction of marine heat flow based on the random forest method and geological and geophysical features - Min Li; Song Huang; Miao Dong; Ya Xu; Tianyao Hao; Xueshan Wu; Yufeng Deng (Marine Geophysical Research, 2021)

Exploring the dynamic mechanism of allosteric drug SHP099 inhibiting SHP2E69K - Shan Du; Xin-hua Lu; Wei-Ya Li; Li-Peng Li; Yang-Chun Ma; Liang Zhou; Jing-Wei Wu; Ying Ma; Run-Ling Wang (Molecular Diversity, 2021)

Quantitative microbial risk assessment for occupational health of temporary entrants and staffs equipped with various grade PPE and exposed to microbial bioaerosols in two WWTPs - Cheng Yan; Ya-li Leng; Jun-ting Wu (International Archives of Occupational and Environmental Health, 2021)

A new ent -kaurane diterpene from Isodon henryi - Xue Jiang; Ling-Xia Zhang; Qing-Mei Feng; Hong Wu; Ya-Lin Liu; De-Qin Wang; Li-Ping Dai; Zhi-Min Wang (Natural Product Research, 2021)

Syntheses and anticancer activities of novel glucosylated (−)-epigallocatechin-3-gallate derivatives linked via triazole rings - Bo-Ya Shi; Ze-Hao Wang; Ning Zhang; Yin-Rong Xie; Xiu-Li Sun; Hao-Nan Yang; Yi-Long Wu; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Medicinal Chemistry Research, 2021)

Enhancement of IUdR Radiosensitization in Cancer Therapy by Low-Energy Transmission X Ray Irradiation - Chien-Chih Ke; Jia-Je Li; Hsueh-Peng Wu; Wen-Wang Kuo; Yi-An Chen; Cheng-Hsiu Lu; Hsin-Ell Wang; Shih-Ming Hsu; Ya-Ju Hsieh; Ren-Shyan Liu (Journal of Medical and Biological Engineering, 2021)

A rapid and accurate method for identifying sexuality of Indarbela obliquifasciata Mell (Lepidoptera, Metarbelidae) adults and pupae - Li-Zhi Huo; Long-Hua Sun; Jing-Ai Zhang; Chao Wu; Ya-Hui Hou; Yong-Yue Wang; Zhi-Jie Li; Jia-Ru Deng; Si-Meng Yang; Ke-Ke Bi (International Journal of Tropical Insect Science, 2021)

Genome-wide identification of GMP genes in Rosaceae and functional characterization of FaGMP4 in strawberry (Fragaria × ananassa) - Yuanxiu Lin; Jiahao Zhang; Lintai Wu; Yunting Zhang; Qing Chen; Mengyao Li; Yong Zhang; Ya Luo; Yan Wang; Xiaorong Wang; Haoru Tang (Genes & Genomics, 2021)

Polymorphisms in the DC-SIGN gene and their association with the severity of hand, foot, and mouth disease caused by enterovirus 71 - Ya-Ping Li; Mu-Qi Wang; Chen-Rui Liu; Hui-Ling Deng; Yuan Wu; Shuang-Suo Dang; Li-Hong Xu (Archives of Virology, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

A Highly Selective Turn‐on Fluorescent and Naked‐eye Colourimetric Dual‐channel Probe for Cyanide Anions Detection in Water Samples - Ya Wu; Wen-Min Ding; Juan Li; Geng Guo; Shu-Zhen Zhang; Hao-Ran Jia; Yin-Xia Sun (Journal of Fluorescence, 2021)

Carnosic acid alleviates depression-like behaviors on chronic mild stressed mice via PPAR-γ-dependent regulation of ADPN/FGF9 pathway - Xiao-qing Wang; Ya-hui Tang; Gui-rong Zeng; Li-feng Wu; Ying-jun Zhou; Ze-neng Cheng; De-Jian Jiang (Psychopharmacology, 2021)

Effects of Different Component Contents of Colistin Methanesulfonate on the Pharmacokinetics of Prodrug and Formed Colistin in Human - Ya-Xin Fan; Yuan-Cheng Chen; Yi Li; Ji-Cheng Yu; Xing-Chen Bian; Xin Li; Wan-Zhen Li; Bei-Ning Guo; Hai-Lan Wu; Xiao-Fen Liu; Yu Wang; Xiao-Yong Xu; et al. (Pharmaceutical Research, 2021)

RAB7L1 Participates in Secondary Brain Injury Induced by Experimental Intracerebral Hemorrhage in Rats - Xiaoxing Tan; Yuchong Wei; Jie Cao; Degang Wu; Niansheng Lai; Ruming Deng; Haiying Li; Haitao Shen; Ya Peng; Xiang Li; Gang Chen (Journal of Molecular Neuroscience, 2021)

The disruption of the MAPKK gene triggering the synthesis of flavonoids in endophytic fungus Phomopsis liquidambaris - Qian Yang; Mei Wu; Ya-Li Zhu; Ya-Qiong Yang; Yan-Zhen Mei; Chuan-Chao Dai (Biotechnology Letters, 2021)

Allotransplantation of adult spinal cord tissues after complete transected spinal cord injury: Long-term survival and functional recovery in canines - He Shen; Shuyu Wu; Xi Chen; Bai Xu; Dezun Ma; Yannan Zhao; Yan Zhuang; Bing Chen; Xianglin Hou; Jiayin Li; Yudong Cao; Xianyong Fu; et al. (Science China Life Sciences, 2020)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Population pharmacokinetics and dose optimization of ceftriaxone for children with community-acquired pneumonia - Muhammad Wasim Khan; Ya-Kun Wang; Yue-E Wu; Bo-Hao Tang; Min Kan; Hai-Yan Shi; Yi Zheng; Bao-Ping Xu; A-Dong Shen; Evelyne Jacqz-Aigrain; Li-Yuan Tian; Wei Zhao (European Journal of Clinical Pharmacology, 2020)

Highly sensitive serological approaches for Pepino mosaic virus detection - Wan-qin He; Jia-yu Wu; Yi-yi Ren; Xue-ping Zhou; Song-bai Zhang; Ya-juan Qian; Fang-fang Li; Jian-xiang Wu (Journal of Zhejiang University-SCIENCE B, 2020)

Constraints of salinity- and sediment-induced stratification on the turbidity maximum in a tidal estuary - Ting Lu; Hao Wu; Fan Zhang; Jiasheng Li; Liang Zhou; Jianjun Jia; Zhanhai Li; Ya Ping Wang (Geo-Marine Letters, 2020)

Tyrosine Hydroxylase Gene Polymorphisms Contribute to Opioid Dependence and Addiction by Affecting Promoter Region Function - Jun-lin Liu; Shao-qing Li; Feng Zhu; Yu-xiang Zhang; Ya-nan Wu; Jing-si Yang; Bao Zhang; Chun-xia Yan (NeuroMolecular Medicine, 2020)

The effect of salt on the evolution of a subsalt sandstone reservoir in the Kuqa foreland basin, western China - Hai Wu; Mengjun Zhao; Qingong Zhuo; Xuesong Lu; Long Wang; Weiqiang Li; Ya Deng (Carbonates and Evaporites, 2020)

Neuronal Activity in the Cerebellum During the Sleep-Wakefulness Transition in Mice - Li-Bin Zhang; Jie Zhang; Meng-Jia Sun; Hao Chen; Jie Yan; Fen-Lan Luo; Zhong-Xiang Yao; Ya-Min Wu; Bo Hu (Neuroscience Bulletin, 2020)

Anti-hypertensive effects of Radix Rehmanniae and its active ingredients - Chiu-Haw Chao; Jue-Liang Hsu; Mu-Fen Chen; Ya-Hu Shih; Chia-Hui Lee; Mei-Li Wu; Chi-I Chang (Natural Product Research, 2020)

Development of a specific AFLP-based SCAR marker for Chinese Race 34MKG of Puccinia graminis f. sp. tritici - Si Chen; Xue Yang; Wen-gong Huang; Yan Liu; Ying Yu; Guang-wen Wu; Shu-quan Zhang; Tian-ya Li; Yuan-yin Cao (Molecular Biology Reports, 2020)

Endophytic colonization by Beauveria bassiana increases the resistance of tomatoes against Bemisia tabaci - Qiu-Yang Wei; Ya-Ying Li; Chen Xu; Yi-Xia Wu; Ya-Ru Zhang; Huai Liu (Arthropod-Plant Interactions, 2020)
Beauveria bassiana , an entomopathogenic fungus, can exist asymptomatically as an endophyte in many plants. This study aimed to determine the efficiency of B. bassiana colonization of tomato plants using different inoculation methods, and how colonization of the host plant affects the key pest of tomato, the whitefly Bemisia tabaci . To confirm fungal colonization efficiency, nested PCR technique was used to detect B. bassiana sequences in Solanum lycopersicum . Distribution of the fungus within the plant parts was determined by selective medium. Tomato growth parameters were determined with plants that had been inoculated using direct spraying or irrigation of the rhizosphere. B. tabaci performance assays were carried out in a cage, and preference to treatments was determined using Y-tube olfactometer studies. Results show that B. bassiana can effectively colonize tomato, with colonization rate using leaf spraying reaching 100% within 14 days. Fungal presence was not uniformly distributed among plant parts, but was biased towards the inoculation sites. For inoculation, conidial suspension sprayed at 1 × 10 8 conidia/ml resulted in the highest number of isolated colonies in leaf tissue, 8.5 ± 2.02 colonies per 2 g of fresh tissue ( F 4,19 = 2.779, P = 0.045), and reached the lowest with root treatment. Although only small differences were observed among the growth indicators, leaf spray inoculation resulted in a significant positive influence on plant growth (PC1 55.7% contributions scores = 2.645) in further Principal component analysis. As for the feeding selectivity, B. tabaci preferred uninoculated plants. In Y-tube olfactometer assay, 80.5% of adults selected uninoculated plants. These findings add to the understanding of the interactions between B. bassiana and plants and indicate the potential of expanding the use of entomopathogenic fungi for crop protection.

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Leukocyte immunoglobulin-like receptor B4 protects against cardiac hypertrophy via SHP-2-dependent inhibition of the NF-κB pathway - Heng Zhou; Ning Li; Yuan Yuan; Ya-Ge Jin; Qingqing Wu; Ling Yan; Zhou-Yan Bian; Wei Deng; Di-Fei Shen; Hongliang Li; Qi-Zhu Tang (Journal of Molecular Medicine, 2020)

Reduction of Human DNA Contamination in Clinical Cerebrospinal Fluid Specimens Improves the Sensitivity of Metagenomic Next-Generation Sequencing - Xin-Chao Ji; Lin-Fu Zhou; Chao-Yang Li; Ya-Jun Shi; Meng-Li Wu; Yun Zhang; Xiao-Fei Fei; Gang Zhao (Journal of Molecular Neuroscience, 2020)

The Fluorescence Property of Zirconium-Based MOFs Adsorbed Sulforhodamine B - Bo Ruan; Huan-Li Liu; Lei Xie; Hui Ding; Ya Zhang; Jin Wu; Zhe Huang; Dean Shi; Tao Jiang; Fang-Chang Tsai (Journal of Fluorescence, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Methamphetamine-Induced Cognitive Deficits and Psychiatric Symptoms Are Associated with Serum Markers of Liver Damage - Tingting Zhao; Changping Zhai; Hongmei Song; Yanhai Wu; Chuanhui Ge; Yonglin Zhang; Hongxia Xu; Zhengsuo Chi; Hui Chu; Wei Shi; Xiaodong Cheng; Xin Li; et al. (Neurotoxicity Research, 2020)

All-trans-retinoic acid generation is an antidotal clearance pathway for all-trans-retinal in the retina - Qing-qing Xia; Ling-min Zhang; Ying-ying Zhou; Ya-lin Wu; Jie Li (Journal of Zhejiang University-SCIENCE B, 2019)

Correction to: Vertical Distributions of Suspended Sediment Concentrations in the Turbidity Maximum Zone of the Periodically and Partially Stratified Changjiang Estuary - Zhanhai Li; Jianjun Jia; Yongsheng Wu; Haibo Zong; Guoan Zhang; Ya Ping Wang; Yang Yang; Liang Zhou; Shu Gao (Estuaries and Coasts, 2019)

Antihyperlipidemic glycosides from the root bark of Lycium chinense - Hui Chen; Yu-Jie Li; Yan-Jun Sun; Xiao-Kun Li; Gong Jian-Hong; Ya Wu; Fang-Yi Su; Kun Du; Yan-Li Zhang; Wei-Sheng Feng (Natural Product Research, 2019)

Rab18 Collaborates with Rab7 to Modulate Lysosomal and Autophagy Activities in the Nervous System: an Overlapping Mechanism for Warburg Micro Syndrome and Charcot-Marie-Tooth Neuropathy Type 2B - Fang-Shin Nian; Lei-Li Li; Chih-Ya Cheng; Pei-Chun Wu; You-Tai Lin; Cheng-Yung Tang; Bo-Shiun Ren; Chin-Yin Tai; Ming-Ji Fann; Lung-Sen Kao; Chen-Jee Hong; Jin-Wu Tsai (Molecular Neurobiology, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

Quantification of cardiac pumping mechanics in rats by using the elastance–resistance model based solely on the measured left ventricular pressure and cardiac output - Chih-Hsien Wang; Ru-Wen Chang; En-Ting Wu; Chun-Yi Chang; Hsien-Li Kao; Ming-Shiou Wu; Ya-Jung Cheng; Yih-Sharng Chen; Kuo-Chu Chang (Pflügers Archiv - European Journal of Physiology, 2019)

Tolerance of two apple rootstocks to short-term salt stress: focus on chlorophyll degradation, photosynthesis, hormone and leaf ultrastructures - Yan-fang Zhu; Yu-xia Wu; Ya Hu; Xu-mei Jia; Tong Zhao; Li Cheng; Yan-xiu Wang (Acta Physiologiae Plantarum, 2019)

Endophytic community of Pb-Zn hyperaccumulator Arabis alpina and its role in host plants metal tolerance - Vijay K. Sharma; Xin-ya Li; Guang-li Wu; Wei-xiao Bai; Shobhika Parmar; James F. White Jr; Hai-yan Li (Plant and Soil, 2019)

Late Jurassic to Early Cretaceous age of the Daqiao gold deposit, West Qinling Orogen, China: implications for regional metallogeny - Ya-Fei Wu; Jian-Wei Li; Katy Evans; Paulo M. Vasconcelos; David S. Thiede; Denis Fougerouse; Kirsten Rempel (Mineralium Deposita, 2019)

Molecular surveillance of coxsackievirus A16 reveals the emergence of a new clade in mainland China - Long Chen; Xiang-Jie Yao; Shao-Jian Xu; Hong Yang; Chun-Li Wu; Jing Lu; Wen-Bo Xu; Hai-Long Zhang; Jun Meng; Yong Zhang; Ya-Qing He; Ren-Li Zhang (Archives of Virology, 2019)

Lycium barbarum polysaccharide attenuates diabetic testicular dysfunction via inhibition of the PI3K/Akt pathway-mediated abnormal autophagy in male mice - Guang-Jiang Shi; Jie Zheng; Xiao-Xu Han; Ya-Ping Jiang; Zhi-Mei Li; Jing Wu; Qing Chang; Yang Niu; Tao Sun; Yu-Xiang Li; Zhen Chen; Jian-Qiang Yu (Cell and Tissue Research, 2018)

Isolation and purification of diterpenoids from the aerial parts of Isodon excisoides target-guided by UPLC-LTQ-Orbitrap-MS - Li-Ping Dai; Ling-Xia Zhang; Ya-Lin Liu; Hong Wu; Rui-Xin Liu; Meng Zhao; Shuang-Shuang Tian; Xue Jiang; Sui-Qing Chen (Natural Product Research, 2018)

Three new 3,4-seco-cycloartane triterpenes from Gardenia sootepensis - Wei-Wu Song; Xue-Qin Wang; Hua-Li Jia; Zheng-Kun Zhang; Yong-Jie Ding; Ya-Hong Chen (Natural Product Research, 2018)

Assessment of anti-diabetic activity of peanut shell polyphenol extracts - Xiao-meng Sun; Hai-qing Ye; Jing-bo Liu; Lei Wu; Ding-bo Lin; Ya-li Yu; Feng Gao (Journal of Zhejiang University-SCIENCE B, 2018)

Molecular insights into brown rust resistance and potential epidemic based on the Bru1 gene in sugarcane varieties and new elite clones - Zhu Li; Ya-Chun Su; Qing Yu; Yun Chen; Shi-Wu Gao; Yong-Gang Zhang; You-Xiong Que; Li-Ping Xu (Euphytica, 2018)

Testing Darwin's transoceanic dispersal hypothesis for the inland nettle family (Urticaceae) - Zeng‐Yuan Wu; Jie Liu; Jim Provan; Hong Wang; Chia‐Jui Chen; Marc W. Cadotte; Ya‐Huang Luo; Bruno S. Amorim; De‐Zhu Li; Richard I. Milne (Ecology Letters, 2018)
Dispersal is a fundamental ecological process, yet demonstrating the occurrence and importance of long‐distance dispersal ( LDD ) remains difficult, having rarely been examined for widespread, non‐coastal plants. To address this issue, we integrated phylogenetic, molecular dating, biogeographical, ecological, seed biology and oceanographic data for the inland Urticaceae. We found that Urticaceae originated in Eurasia c . 69 Ma, followed by ≥ 92 LDD events between landmasses. Under experimental conditions, seeds of many Urticaceae floated for > 220 days, and remained viable after 10 months in seawater, long enough for most detected LDD events, according to oceanographic current modelling. Ecological traits analyses indicated that preferences for disturbed habitats might facilitate LDD . Nearly half of all LDD events involved dioecious taxa, so population establishment in dioecious Urticaceae requires multiple seeds, or occasional selfing. Our work shows that seawater LDD played an important role in shaping the geographical distributions of Urticaceae, providing empirical evidence for Darwin's transoceanic dispersal hypothesis.

Effects of autophagy on acid-sensing ion channel 1a-mediated apoptosis in rat articular chondrocytes - Ya-Ya Xie; Yue Li; Ren-peng Zhou; Bei-Bei Dai; Yue-jiao Qian; Xiao-shan Wu; Jin-fang Ge; Wei Hu; Fei-hu Chen (Molecular and Cellular Biochemistry, 2018)

Occurrence and health risk assessment of organotins in waterworks and the source water of the Three Gorges Reservoir Region, China - Ting Deng; Lei Wu; Jun-Min Gao; Bin Zhou; Ya-Li Zhang; Wen-Nan Wu; Zhuo-Heng Tang; Wen-Chao Jiang; Wei-Lin Huang (Environmental Science and Pollution Research, 2018)

Effect of Bacterial Community and Free Amino Acids on the Content of Biogenic Amines During Fermentation of Yu-lu, a Chinese Fermented Fish Sauce - Yueqi Wang; Chunsheng Li; Laihao Li; Xianqing Yang; Yanyan Wu; Yongqiang Zhao; Ya Wei (Journal of Aquatic Food Product Technology, 2018)

A new pair of enantiomeric lignans from the fruits of Morinda citrifolia and their absolute configuration - Wen-Jian Liu; Yue-Juan Chen; Dan-Na Chen; Ya-Ping Wu; Yu-Jie Gao; Jing Li; Wen-Jun Zhong; Lin Jiang (Natural Product Research, 2018)

Longitudinal dynamic impedance of a static drill rooted nodular pile embedded in layered soil - Zhen-Ya Li; Kui-Hua Wang; Wen-Bing Wu; Chin Jian Leo (Marine Georesources & Geotechnology, 2018)

Polyphasic taxonomic characterisation of a novel strain as Pararhizobium haloflavum sp. nov., isolated from soil samples near a sewage treatment tank - Xia Shen; Yu Li; Zhe Zhao; Yi-Fan Han; Wen-Wu Zhang; Xiao-Yun Yu; Chong-Ya Zhang; Cong Sun; Min Wu (Antonie van Leeuwenhoek, 2018)

Sarsasapogenin suppresses Aβ overproduction induced by high glucose in HT-22 cells - Meng-Ya Zhang; Yu Li; Shen-Yuan Yin; Li Kong; Xiao-Li Liu; Xiao-Xing Yin; Yao-Wu Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Establishment and characterization of a kidney cell line from kelp grouper Epinephelus moara - Xiao-Feng Liu; Ya-Hong Wu; Shi-Na Wei; Na Wang; Peng-Fei Li; Yang-Zhen Li; Nian-Wei Zhang; Qi-Wei Qin; Song-Lin Chen (Fish Physiology and Biochemistry, 2018)

Optimization of Weight Ratio for DSPE-PEG/TPGS Hybrid Micelles to Improve Drug Retention and Tumor Penetration - Ya Jin; Zimei Wu; Caibin Li; Weisai Zhou; John P. Shaw; Bruce C. Baguley; Jianping Liu; Wenli Zhang (Pharmaceutical Research, 2018)

Regulation of fine particulate matter (PM2.5) in the Pacific Rim: perspectives from the APRU Global Health Program - Chang-Fu Wu; Alistair Woodward; Ya-Ru Li; Haidong Kan; Rajasekhar Balasubramanian; Mohd Talib Latif; Mazrura Sahani; Tsun-Jen Cheng; Chia-Pin Chio; Nutta Taneepanichskul; Ho Kim; Chang-Chuan Chan; et al. (Air Quality, Atmosphere & Health, 2017)

Early Cretaceous continental arc-related volcanic rocks in the Duobuzha area, northern Tibet: implications for evolution history of the Bangong–Nujiang Ocean - Tian-Yu Zhang; Chao-Ming Xie; Cai Li; Jian-Jun Fan; Ming Wang; Ya-Dong Wu (International Geology Review, 2017)

Expression of Iron Transporters and Pathological Hallmarks of Parkinson’s and Alzheimer’s Diseases in the Brain of Young, Adult, and Aged Rats - Li-Na Lu; Zhong-Ming Qian; Ka-Chun Wu; Wing-Ho Yung; Ya Ke (Molecular Neurobiology, 2017)

Mangiferin Upregulates Glyoxalase 1 Through Activation of Nrf2/ARE Signaling in Central Neurons Cultured with High Glucose - Yao-Wu Liu; Ya-Qin Cheng; Xiao-Li Liu; Yun-Chao Hao; Yu Li; Xia Zhu; Fan Zhang; Xiao-Xing Yin (Molecular Neurobiology, 2017)

Geochemistry and geochronology of the mafic dikes in the Taipusi area, northern margin of North China Craton: Implications for Silurian tectonic evolution of the Central Asian Orogen - Jing-Hua Wu; Huan Li; Xiao-Shuang Xi; Hua Kong; Qian-Hong Wu; Neng-Li Peng; Xi-Ming Wu; Jing-Ya Cao; Jillian Aira S Gabo-Ratio (Journal of Earth System Science, 2017)

AKTs/PKBs: molecular characterization, tissue expression and transcriptional responses to insulin and/or wortmannin in yellow catfish Pelteobagrus fulvidraco - Mei-Qin Zhuo; Ya-Xiong Pan; Kun Wu; Yi-Huan Xu; Li-Han Zhang; Zhi Luo (Fish Physiology and Biochemistry, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

IRS1 and IRS2: molecular characterization, tissue expression and transcriptional regulation by insulin in yellow catfish Pelteobagrus fulvidraco - Mei-Qin Zhuo; Ya-Xiong Pan; Kun Wu; Yi-Huan Xu; Li-Han Zhang; Zhi Luo (Fish Physiology and Biochemistry, 2017)

Polybrominated diphenyl ethers, organochlorine pesticides, and polycyclic aromatic hydrocarbons in water from the Jiulong River Estuary, China: levels, distributions, influencing factors, and risk assessment - Yuling Wu; Xinhong Wang; Yongyu Li; Miaolei Ya; Hui Luo; Huasheng Hong (Environmental Science and Pollution Research, 2017)

Simulating climate change impacts and potential adaptations on rice yields in the Sichuan Basin, China - Che-Chen Xu; Wen-Xiang Wu; Quan-Sheng Ge; Yang Zhou; Yu-Mei Lin; Ya-Mei Li (Mitigation and Adaptation Strategies for Global Change, 2017)

GPR30 Activation Contributes to the Puerarin-Mediated Neuroprotection in MPP+-Induced SH-SY5Y Cell Death - Yue-Fa Cheng; Guoqi Zhu; Qing-Wen Wu; Yue-Sheng Xie; Yan Jiang; Lan Guo; Ya-Li Guan; Ying-Shuo Liu; Jun Zhang (Journal of Molecular Neuroscience, 2017)

Effects of freeze-thaw cycle on engineering properties of loess used as road fills in seasonally frozen ground regions, North China - Guo-yu Li; Wei Ma; Yan-hu Mu; Fei Wang; Shan-zhi Fan; Ya-hu Wu (Journal of Mountain Science, 2017)

Size Effects on the Interaction of QDs with the Mitochondrial Membrane In Vitro - Lu Lai; Ya-Ping Li; Ping Mei; Wu Chen; Feng-Lei Jiang; Yi Liu (The Journal of Membrane Biology, 2016)

The status evaluation of the permafrost environment along the Chaida’er-Muli Railway in southern Qilian Mountains in northern Qinghai Province, China - Wei Cao; Yu Sheng; Ya-ling Chou; Ji-chun Wu; Jing Li; Sheng-ting Wang (Journal of Mountain Science, 2016)

Effects of land use conversion and fertilization on CH4 and N2O fluxes from typical hilly red soil - Huifeng Liu; Guohua Liu; Ya Li; Xing Wu; Dan Liu; Xiaoqin Dai; Ming Xu; Fengting Yang (Environmental Science and Pollution Research, 2016)

Activation of mTOR signaling mediates the increased expression of AChE in high glucose condition: in vitro and in vivo evidences - Yao-Wu Liu; Liang Zhang; Yu Li; Ya-Qin Cheng; Xia Zhu; Fan Zhang; Xiao-Xing Yin (Molecular Neurobiology, 2016)

Quantitative determination constraints on dolomitization model for the Upper Permian Changxing reservoir dolomites of Northeastern Sichuan Basin, Southwestern China - Rui Zhao; Ya Sheng Wu; Hong Xia Jiang; Qing Song Liu; Li Jing Liu (Carbonates and Evaporites, 2016)

Genetic Diversity Analysis of Sugarcane Germplasm Based on Fluorescence-Labeled Simple Sequence Repeat Markers and a Capillary Electrophoresis-based Genotyping Platform - Qian You; Yong-Bao Pan; Li-Ping Xu; Shi-Wu Gao; Qin-Nan Wang; Ya-Chun Su; Yong-Qing Yang; Qi-Bin Wu; Ding-Gang Zhou; You-Xiong Que (Sugar Tech, 2016)

Cerebral blood flow changes in hemodialysis and peritoneal dialysis patients: an arterial-spin labeling MR imaging - Xiao Lu Jiang; Ji Qiu Wen; Long Jiang Zhang; Gang Zheng; Xue Li; Zhe Zhang; Ya Liu; Li Juan Zheng; Long Wu; Hui Juan Chen; Xiang Kong; Song Luo; et al. (Metabolic Brain Disease, 2016)

Isolation and identification of polyphenols from Marsilea quadrifolia with antioxidant properties in vitro and in vivo - Yuan Zhang; Hai-Yan Tian; Ya-Fang Tan; Yuk-Lau Wong; Hoi Yan Wu; Jun-Feng Jia; Guo-En Wang; Jing-Jing Gao; Yi-Fang Li; Hiroshi Kurihara; Pang-Chui Shaw; Ren-Wang Jiang (Natural Product Research, 2016)

The Analysis Method of Rock Mass Deformation of Large Cross-section Tunnel - Chun-hui Chen; Li Wu; Ya-xiong Peng (Geotechnical and Geological Engineering, 2016)

Complete genome sequence of a distinct calla lily chlorotic spot virus isolated in mainland China - Ye Xu; Si-bo Wang; Yong-zhong Li; Hong-zheng Tao; Ya-ning Huang; Bao-wei Wu; Yu-mei Dong; John Hu; Ya-ting Liu (Archives of Virology, 2016)

Radix ranunculus temate saponins induces apoptosis via the death receptor and mitochondrial pathways in SGC-7901 cells - Mao-lin Li; Han-min Gu; Hong-ya Hang; Yao-li Jiang; Jiao Jiang; Qian-na Gu; Wen-yan Wu (Molecular & Cellular Toxicology, 2015)

The roles of methanogens and acetogens in dechlorination of trichloroethene using different electron donors - Li-Lian Wen; Yin Zhang; Ya-Wei Pan; Wen-Qi Wu; Shao-Hua Meng; Chen Zhou; Youneng Tang; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2015)

Differential protein expression analysis following olfactory learning in Apis cerana - Li-Zhen Zhang; Wei-Yu Yan; Zi-Long Wang; Ya-Hui Guo; Yao Yi; Shao-Wu Zhang; Zhi-Jiang Zeng (Journal of Comparative Physiology A, 2015)

Reproductive management through integration of PGD and MPS-based noninvasive prenatal screening/diagnosis for a family with GJB2-associated hearing impairment - WenPing Xiong; DaYong Wang; Yuan Gao; Ya Gao; HongYang Wang; Jing Guan; Lan Lan; JunHao Yan; Liang Zong; Yuan Yuan; Wei Dong; SeXin Huang; et al. (Science China Life Sciences, 2015)

Simultaneous detection of three wheat pathogenic fungal species by multiplex PCR - Si Chen; Yuan-yin Cao; Tian-ya Li; Xian-xin Wu (Phytoparasitica, 2015)

The prevalence and determinants of drug-resistance-associated mutations in the HIV-1-infected MSM population of Henan Province in China - Li-Juan Hou; Hong-Wei Wang; Shu-Peng Duan; Ya Zhuo; Yan-Cai Zhou; Hong-Jie Wu; Bao-Sheng Shen (Archives of Virology, 2015)

Helicobacter pylori with the Intact dupA Cluster is more Virulent than the Strains with the Incomplete dupA Cluster - Ming-yi Wang; Chen Shao; Jie Li; Ya-Chao Yang; Shao-bo Wang; Jun-ling Hao; Chun-mei Wu; Xiao-zhong Gao; Shi-he Shao (Current Microbiology, 2015)

Effect of dietary supplementation of Bacillus subtilis B10 on biochemical and molecular parameters in the serum and liver of high-fat diet-induced obese mice - Kai Lei; Ya-li Li; Yang Wang; Jing Wen; Hong-zhao Wu; Dong-you Yu; Wei-fen Li (Journal of Zhejiang University-SCIENCE B, 2015)

Establishment and characterization of fin cell lines from diploid, triploid, and tetraploid oriental weatherfish (Misgurnus anguillicaudatus) - Xia Li; Chen Ma; Yan-Jie Qin; Ya-Juan Li; Di Wu; Li-Wen Bai; Ai-Jun Pei (Fish Physiology and Biochemistry, 2015)

Smooth muscle 22α facilitates angiotensin II-induced signaling and vascular contraction - Xiao-Li Xie; Xi Nie; Jun Wu; Fan Zhang; Li-Li Zhao; Yan-Ling Lin; Ya-Juan Yin; Hui Liu; Ya-Nan Shu; Sui-Bing Miao; Huan Li; Peng Chen; et al. (Journal of Molecular Medicine, 2015)

Association between the CYP1A2 polymorphisms and risk of cancer: a meta-analysis - Wen-Xia Sun; Ying-Hua Chen; Zhi-Zhong Liu; Jian-Jun Xie; Wei Wang; Ya-Ping Du; Yu Chen; Xu-Liang Shen; Xiao-Feng He; Li-Xia Wu; Wu Wei; Lin Zhang (Molecular Genetics and Genomics, 2015)

Prognostic Factors of Survival in Pathologic Incomplete Response Patients with Locally Advanced Breast Cancer After Neoadjuvant Chemotherapy - Ou Huang; Min Jiang; Xiao-song Chen; Jia-yi Wu; Wei-guo Chen; Ya-fei Li; Kun-wei Shen (Cell Biochemistry and Biophysics, 2015)

Neurochemical properties of the synapses between the parabrachial nucleus-derived CGRP-positive axonal terminals and the GABAergic neurons in the lateral capsular division of central nucleus of amygdala - Ya-Cheng Lu; Yan-Zhou Chen; Yan-Yan Wei; Xiao-Tao He; Xia Li; Wei Hu; Yuchio Yanagawa; Wen Wang; Sheng-Xi Wu; Yu-Lin Dong (Molecular Neurobiology, 2015)

Nicotine-induced upregulation of VCAM-1, MMP-2, and MMP-9 through the α7-nAChR-JNK pathway in RAW264.7 and MOVAS cells - Zong-Zhuang Li; Zhen-Zhen Guo; Zhi Zhang; Qun-An Cao; Ya-Juan Zhu; Hua-Li Yao; Li-Li Wu; Qiu-Yan Dai (Molecular and Cellular Biochemistry, 2015)

Lipopolysaccharides Upregulate Hepcidin in Neuron via Microglia and the IL-6/STAT3 Signaling Pathway - Zhong-Ming Qian; Xuan He; Tuo Liang; Ka-Chun Wu; Yik-Chun Yan; Li-Na Lu; Guang Yang; Qian Qian Luo; Wing-Ho Yung; Ya Ke (Molecular Neurobiology, 2014)

miR-1246 releases RTKN2-dependent resistance to UVB-induced apoptosis in HaCaT cells - Wei Li; Ya-Fen Wu; Rong-Hua Xu; Hui Lu; Cui Hu; Hua Qian (Molecular and Cellular Biochemistry, 2014)

Large-scale screening maize germplasm for low-phosphorus tolerance using multiple selection criteria - Li-tian Zhang; Jia Li; Ting-zhao Rong; Shi-bin Gao; Feng-kai Wu; Jie Xu; Meng-lu Li; Mo-ju Cao; Jing Wang; Er-liang Hu; Ya-xi Liu; Yan-li Lu (Euphytica, 2014)

Characterization of OsDREB6 responsive to osmotic and cold stresses in rice - Ya-Guang Ke; Zhi-Jun Yang; Shun-Wu Yu; Tian-Fei Li; Jin-Hong Wu; Huan Gao; Ya-Ping Fu; Li-Jun Luo (Journal of Plant Biology, 2014)

Monitoring and modeling the effects of groundwater flow on arsenic transport in Datong Basin - Qian Yu; Yanxin Wang; Rui Ma; Chunli Su; Ya Wu; Junxia Li (Journal of Earth Science, 2014)

Ovalbumin enhances YKL-40, IL-5, GM-CSF, and eotaxin expression simultaneously in primarily cultured mouse tracheal epithelial cells - Su-qin Ben; Ya-li Qiu; Juan Zhou; Xiao-yu Zhou; Shan Zhang; Yi Wu; Shao-qing Ju; Song-shi Ni (In Vitro Cellular & Developmental Biology - Animal, 2014)

Epigallocatechin-3-gallate induces apoptosis, inhibits proliferation and decreases invasion of glioma cell - Hong Li; Zhe Li; Ya-Ming Xu; Yue Wu; Kang-Kang Yu; Can Zhang; Yong-Hua Ji; Gang Ding; Fu-Xue Chen (Neuroscience Bulletin, 2014)

Runoff characteristics of the Nen River Basin and its cause - Hong-yan Li; Yu-xin Wang; Li-na Jia; Ya-nan Wu; Miao Xie (Journal of Mountain Science, 2014)

Production and molecular characterization of diploid and tetraploid somatic cybrid plants between male sterile Satsuma mandarin and seedy sweet orange cultivars - Shi-Xin Xiao; Manosh Kumar Biswas; Meng-Ya Li; Xiu-Xin Deng; Qiang Xu; Wen-Wu Guo (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Synthesis and antibacterial evaluation of furan derivatives bearing a rhodanine moiety - Jian Che; Chang-Ji Zheng; Ming-Xia Song; Ya-Jing Bi; Yi Liu; Yin-Jing Li; Yan Wu; Liang-Peng Sun; Hu-Ri Piao (Medicinal Chemistry Research, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Major geochemical controls on fluoride enrichment in groundwater: A case study at Datong Basin, northern China - Liang Li; Yanxin Wang; Ya Wu; Junxia Li (Journal of Earth Science, 2013)

Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Fang Liu; Min Wu; Yan-huan Feng; Hui Zhong; Tian-lei Cui; You-qun Huang; Ya-ping Liang; Yong-shu Diao; Li Zang; Ling Li; Jing Zang; Hong-yu Qiu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Hierarchically Clustering to 1,033 Genes Differentially Expressed in Mouse Superior Colliculus in the Courses of Optic Nerve Development and Injury - Qiang Mei; Yan-qi Zhang; Jian-jun Liu; Cheng-ren Li; Xing-shu Chen; Hong-li Li; Mao-lin Qin; Ya-zhou wu; Yun-lai Liu; Wen-qin Cai (Cell Biochemistry and Biophysics, 2013)

Improvement of mid- to long-term runoff forecasting based on physical causes: application in Nenjiang basin, China - Hong-Yan Li; Lin Tian; Ya-nan Wu; Miao Xie (Hydrological Sciences Journal, 2013)

Molecular cloning and characterization of two pathogenesis-related β-1,3-glucanase genes ScGluA1 and ScGluD1 from sugarcane infected by Sporisorium scitamineum - Ya-chun Su; Li-ping Xu; Ban-tong Xue; Qi-bin Wu; Jin-long Guo; Lu-guang Wu; You-xiong Que (Plant Cell Reports, 2013)

Discrimination between Demodex folliculorum (Acari: Demodicidae) isolates from China and Spain based on mitochondrial cox1 sequences - Ya-e Zhao; Jun-xian Ma; Li Hu; Li-ping Wu; Manuel De Rojas (Journal of Zhejiang University-SCIENCE B, 2013)

Structures and biogenetic analysis of lipofuscin bis-retinoids - Ya-lin Wu; Jie Li; Ke Yao (Journal of Zhejiang University-SCIENCE B, 2013)

Effects of perfluorooctanesulfonate and perfluorobutanesulfonate on the growth and sexual development of Xenopus laevis - Qin-Qin Lou; Yin-Feng Zhang; Zhen Zhou; Ya-Li Shi; Ya-Nan Ge; Dong-Kai Ren; Hai-Ming Xu; Ya-Xian Zhao; Wu-Ji Wei; Zhan-Fen Qin (Ecotoxicology, 2013)

Suppression of methylglyoxal hyperactivity by mangiferin can prevent diabetes-associated cognitive decline in rats - Yao-Wu Liu; Xia Zhu; Qian-Qian Yang; Qian Lu; Jian-Yun Wang; Hui-Pu Li; Ya-Qin Wei; Jia-Le Yin; Xiao-Xing Yin (Psychopharmacology, 2013)

Up-regulation of Slc39A2(Zip2) mRNA in peripheral blood mononuclear cells from patients with pulmonary tuberculosis - Yan-ting Tao; Qing Huang; Ya-li Jiang; Xiao-lei Wang; Ping Sun; Yuanyuan Tian; Hai-liang Wu; Min Zhang; Si-bo Meng; Yu-shu Wang; Qing Sun; Lian-ying Zhang (Molecular Biology Reports, 2013)

Short-chain chlorinated paraffins (SCCPs) in surface soil from a background area in China: occurrence, distribution, and congener profiles - Xue-Tong Wang; Yuan Zhang; Yi Miao; Ling-Ling Ma; Yuan-Cheng Li; Yue-Ya Chang; Ming-Hong Wu (Environmental Science and Pollution Research, 2013)

Paracoccus zhejiangensis sp. nov., isolated from activated sludge in wastewater-treatment system - Zhi-Guo Wu; Dao-Feng Zhang; Ya-Long Liu; Fang Wang; Xin Jiang; Chao Li; Shun-Peng Li; Qing Hong; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Reduction of connexin43 in human endothelial progenitor cells impairs the angiogenic potential - Hsueh-Hsiao Wang; Cheng-Huang Su; Yih-Jer Wu; Jiun-Yi Li; Ya-Ming Tseng; Yi-Chun Lin; Chin-Ling Hsieh; Cheng-Ho Tsai; Hung-I Yeh (Angiogenesis, 2013)

Astrocyte-Derived Sonic Hedgehog Contributes to Angiogenesis in Brain Microvascular Endothelial Cells via RhoA/ROCK Pathway After Oxygen–Glucose Deprivation - Quan-Wei He; Yuan-Peng Xia; Sheng-Cai Chen; Yong Wang; Ming Huang; Yan Huang; Jian-Yong Li; Ya-Nan Li; Yuan Gao; Ling Mao; Yuan-Wu Mei; Bo Hu (Molecular Neurobiology, 2013)

Quaternary palaeoenvironmental oscillations drove the evolution of the Eurasian Carassius auratus complex (Cypriniformes, Cyprinidae) - Yun Gao; Shu‐Yan Wang; Jing Luo; Robert W. Murphy; Rui Du; Shi‐Fang Wu; Chun‐Ling Zhu; Yan Li; Andrei D. Poyarkov; Sang Ngoc Nguyen; Peng‐Tao Luan; Ya‐Ping Zhang (Journal of Biogeography, 2012)
Aim We sought to reconstruct the spatio‐temporal genetic diversification in goldfish of the Carassius auratus complex, which is widely distributed in Eurasia, to test whether vicariance events or human‐mediated translocations best explained lineage divergence and genogeographical history. Location East Asia and the Oriental islands including Japan, the Ryukyus and Taiwan, and Europe, including Russia and the Czech Republic. Methods We reconstructed the matrilineal history of Eurasian goldfish using 1876 sequences from the partial mitochondrial DNA control region (426 bp) and 191 complete sequences of cytochrome b (1140 bp) from 67 localities representing most of the range of the species. Divergence times were estimated using a Bayesian Markov chain Monte Carlo approach based either on molecular clock data or on the fossil record. Genetic structure and the historical demography of populations were analysed using partial correlation tests and analyses of molecular variance. Results Three lineages had high levels of regional specificity. Lineages A and B from the main islands of Japan differed greatly from lineage C, which occurred on the mainland, Taiwan and the Ryukyus. Lineages A and B had late Pliocene origins. Six geographically constrained sublineages within lineage C had near‐simultaneous mid‐Pleistocene divergences. Main conclusions Genetic structure in the C. auratus complex appears to have been driven by palaeoenvironmental perturbations rather than human translocations. The disappearance of a land bridge in the Tsushima Strait around 3.0 Ma is responsible for the separation of Japanese and continental lineages; the estimated divergence time is 2.75–2.32 Ma. Fujian, China and Vietnam appear to have provided important refugia for the C. auratus complex during glaciation. After warm, moist summer monsoons intensified during the mid‐Pleistocene, goldfish are likely to have dispersed north‐eastwards to recolonize the Ryukyus via Taiwan and northwards to recolonize mainland China.

Cloning arginine kinase gene and its RNAi in Bursaphelenchus xylophilus causing pine wilt disease - Xin-rong Wang; Xi Cheng; Ya-dong Li; Jin-ai Zhang; Zhi-fen Zhang; Han-rong Wu (European Journal of Plant Pathology, 2012)

Physiological and molecular responses of broad bean (Vicia faba L.) to aluminum stress - Qi Chen; Kong-Huan Wu; Ya-Nan Zhang; Xuan-Huyen Phan; Kun-Zhi Li; Yong-Xiong Yu; Li-Mei Chen (Acta Physiologiae Plantarum, 2012)

Association of 10q23 with colorectal cancer in a Chinese population - Fen-Xia Li; Xue-Xi Yang; Xuan-Qiu He; Ni-Ya Hu; Ying-Song Wu; Ming Li (Molecular Biology Reports, 2012)

Association of STAT4 rs7574865 polymorphism with autoimmune diseases: a meta-analysis - Ya-ling Liang; Hua Wu; Xi Shen; Pei-qiang Li; Xiao-qing Yang; Li Liang; Wei-hua Tian; Li-feng Zhang; Xiao-dong Xie (Molecular Biology Reports, 2012)

CDH1 gene polymorphisms, plasma CDH1 levels and risk of gastric cancer in a Chinese population - Zhen Zhan; Juan Wu; Jun-feng Zhang; Ya-ping Yang; Shujuan Tong; Chun-bing Zhang; Jin Li; Xue-wen Yang; Wei Dong (Molecular Biology Reports, 2012)

Inhibition of Japanese Encephalitis Virus Infection by the Sulfated Polysaccharide Extracts from Ulva lactuca - Ya-Huang Chiu; Yi-Lin Chan; Tsung-Lin Li; Chang-Jer Wu (Marine Biotechnology, 2012)

Erratum to: Correlations of Trace Element levels in the Diet, Blood, Urine and Feces in the Chinese Male - Ying Wang; Yang-Li Ou; Ya-Qiong Liu; Qing Xie; Qing-Fen Liu; Quan Wu; Ti-Qiang Fan; Lai-Lai Yan; Jing-Yu Wang (Biological Trace Element Research, 2012)

Mountain effect and differences in storm floods between northern and southern sources of the Songhua River Basin - Hongyan Li; Ya’nan Wu; Xiubin Li (Journal of Mountain Science, 2012)

Cloning and ontogenetic expression of the uncoupling protein 1 gene UCP1 in sheep - Ya-Nan Yuan; Wen-Zhong Liu; Jian-Hua Liu; Li-Ying Qiao; Jian-Liang Wu (Journal of Applied Genetics, 2012)

A meta-analysis of association between acne vulgaris and Demodex infestation - Ya-e Zhao; Li Hu; Li-ping Wu; Jun-xian Ma (Journal of Zhejiang University-SCIENCE B, 2012)

Postural activity and motion sickness during video game play in children and adults - Chih-Hui Chang; Wu-Wen Pan; Li-Ya Tseng; Thomas A. Stoffregen (Experimental Brain Research, 2012)

Characterization of acute renal allograft rejection by proteomic analysis of renal tissue in rat - Gang Chen; Jing-bin Huang; Jie Mi; Yun-feng He; Xiao-hou Wu; Chun-li Luo; Si-min Liang; Jia-bing Li; Ya-xiong Tang; Jie Li (Molecular Biology Reports, 2012)

Correlations of Trace Element Levels in the Diet, Blood, Urine, and Feces in the Chinese Male - Ying Wang; Yang-Li Ou; Ya-Qiong Liu; Qing Xie; Qing-Fen Liu; Quan Wu; Ti-Qiang Fan; Lai-Lai Yan; Jing-Yu Wang (Biological Trace Element Research, 2012)

Removal of genotoxicity in chlorinated secondary effluent of a domestic wastewater treatment plant during dechlorination - Qian-Yuan Wu; Yi Li; Hong-Ying Hu; Ya-Nan Ding; Huang Huang; Feng-Yun Zhao (Environmental Science and Pollution Research, 2012)

Facial dermatosis associated with Demodex: a case-control study - Ya-e Zhao; Yan Peng; Xiang-lan Wang; Li-ping Wu; Mei Wang; Hu-ling Yan; Sheng-xiang Xiao (Journal of Zhejiang University-SCIENCE B, 2011)

Influence of temperature and medium on viability of Demodex folliculorum and Demodex brevis (Acari: Demodicidae) - Ya-E Zhao; Na Guo; Li-Ping Wu (Experimental and Applied Acarology, 2011)

Genetic polymorphism analysis of 15 STR loci in Chinese Hui ethnic group residing in Qinghai province of China - Ya-jun Deng; Bo-feng Zhu; Chun-mei Shen; Hong-dan Wang; Jing-feng Huang; Yuan-zhe Li; Hai-xia Qin; Hao-fang Mu; Jie Su; Jie Wu; Bo Zhang; Shuan-liang Fan (Molecular Biology Reports, 2011)

He and Ar isotopic compositions and genetic implications for the giant Shizhuyuan W–Sn–Bi–Mo deposit, Hunan Province, South China - Li-Yan Wu; Rui-Zhong Hu; Jian-Tang Peng; Xian-Wu Bi; Guo-Hao Jiang; Hong-Wei Chen; Qiao-Yun Wang; Ya-Ying Liu (International Geology Review, 2011)

Genetic analysis of starch paste viscosity parameters in glutinous rice (Oryza sativa L.) - Chang-Jie Yan; Zhi-Xi Tian; Yu-Wei Fang; Ya-Chun Yang; Jian Li; Sheng-Yuan Zeng; Shi-Liang Gu; Chen-Wu Xu; Shu-Zhu Tang; Ming-Hong Gu (Theoretical and Applied Genetics, 2011)

Norovirus Gastroenteritis Outbreak is Associated with Contaminated Drinking Water in South China - Ya-Qing He; Han-Wu Ma; Xiang-Jie Yao; Qing-Lan Bu; Hong Yang; Wei Huang; Yong-Xiang Duan; Hai-Long Zhang; Chuan-Wen Dai; Wei-Ke Li; Shou-Yi Yu (Food and Environmental Virology, 2010)

Three cotton homeobox genes are preferentially expressed during early seedling development and in response to phytohormone signaling - Yong-Fang Qin; Deng-Di Li; Ya-Jie Wu; Zhi-Hao Liu; Jie Zhang; Yong Zheng; Xue-Bao Li (Plant Cell Reports, 2010)

Development of real-time and nested RT-PCR to detect astrovirus and one-year survey of astrovirus in Jiangmen City, China - Ying-chun Dai; Qiao-hua Xu; Xian-bo Wu; Gui-fang Hu; Ya-li Tang; Jian-dong Li; Qing Chen; Jun Nie (Archives of Virology, 2010)

The promoting role of an isolate of dark-septate fungus on its host plant Saussurea involucrata Kar. et Kir. - Li-qin Wu; Ya-li Lv; Zhi-xia Meng; Juan Chen; Shun-Xing Guo (Mycorrhiza, 2010)

Activation of Group III Metabotropic Glutamate Receptor Reduces Intracellular Calcium in β-Amyloid Peptide [31–35]-Treated Cortical Neurons - Li Zhao; Shen Ting Zhao; Zhong Ming Qian; Ce Zhang; Xiao Mei Wu; Fang Du; Ya Ke (Neurotoxicity Research, 2009)

A semi-supervised learning based method: Laplacian support vector machine used in diabetes disease diagnosis - Jiang Wu; Yuan-Bo Diao; Meng-Long Li; Ya-Ping Fang; Dai-Chuan Ma (Interdisciplinary Sciences: Computational Life Sciences, 2009)

Expressions of three cotton genes encoding the PIP proteins are regulated in root development and in response to stresses - Deng-Di Li; Ya-Jie Wu; Xiang-Mei Ruan; Bing Li; Li Zhu; Hong Wang; Xue-Bao Li (Plant Cell Reports, 2009)

Simultaneous detection of human enterovirus 71 and coxsackievirus A16 in clinical specimens by multiplex real-time PCR with an internal amplification control - Xing-Long Xiao; Ya-Qing He; Yi-Gang Yu; Hong Yang; Gu Chen; Hui-Fang Li; Jing-Wei Zhang; Dong-Mei Liu; Xiao-Feng Li; Xiao-Quan Yang; Hui Wu (Archives of Virology, 2009)

Arsenic exposure, urinary arsenic speciation, and the incidence of urothelial carcinoma: a twelve-year follow-up study - Yung-Kai Huang; Ya-Li Huang; Yu-Mei Hsueh; Mo-Hsiung Yang; Meei-Maan Wu; Shu-Yuan Chen; Ling-I Hsu; Chien-Jen Chen (Cancer Causes & Control, 2008)

Interaction of MT1-MMP and laminin-5γ2 chain correlates with metastasis and invasiveness in human esophageal squamous cell carcinoma - Xiao-Ming Shen; Yu-Peng Wu; Yan-Bin Feng; Man-Li Luo; Xiao-Li Du; Yu Zhang; Yan Cai; Xin Xu; Ya-Ling Han; Xun Zhang; Qi-Min Zhan; Ming-Rong Wang (Clinical & Experimental Metastasis, 2007)

Polyacetylenes Function as Anti-Angiogenic Agents - Li-Wha Wu; Yi-Ming Chiang; Hsiao-Ching Chuang; Sheng-Yang Wang; Ga-Wen Yang; Ya-Huey Chen; Ling-Ya Lai; Lie-Fen Shyur (Pharmaceutical Research, 2004)

Protective effects of adenoviral cardiotrophin-1 gene transfer on rubrospinal neurons after spinal cord injury in adult rats - Zheng-Feng Zhang; Wei-Hong Liao; Qing-Feng Yang; Hong-Yun Li; Ya-Min Wu; Xin-Fu Zhou (Neurotoxicity Research, 2003)

Low Genetic Variation of the Yunnan Hare (Lepus comus G. Allen 1927) as Revealed by Mitochondrial Cytochrome b Gene Sequences - Chun-Hua Wu; Hai-Peng Li; Ying-Xiang Wang; Ya-Ping Zhang (Biochemical Genetics, 2000)